Electroluminescent fiber, yarn and fabric and preparation method thereof
By adopting an electroluminescent fiber design with a simple structure, including a combination of a conductive layer and a luminescent layer, and using a thermal softening drawing method to prepare the fiber, the problems of complex processes, high costs, and difficulty in mass production in the existing technology are solved, and high brightness is achieved. , low-cost, easy to prepare in batches electroluminescent fibers.
Patent Information
- Application Number
- CN202111509616.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-10
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-12-10
AI Technical Summary
In the prior art, the process of preparing electroluminescent fibers is complex and costly, making it difficult to achieve mass production. The brightness of the fibers is limited by the luminous intensity of the central area. The hydrogel electrode is greatly affected by the environment, making it difficult to control the wire diameter and structure.
The optical fiber design with a simple structure is used, including more than two conductive layers and the luminous layer set between the conductive layer. The transparent conductive layer prepares fiber through thermal softness.
The electroluminescent fiber is realized to be high-brightness, low-cost, easy to prepare in batches, controllable in wire diameter, controllable in structure, environmentally friendly, and suitable for a variety of application scenarios.
Smart Images

Figure CN116288766B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of functional fibers, and specifically to an electroluminescent fiber, yarn and fabric and a preparation method thereof. Background Art
[0002] With the improvement of the quality of life, people have higher and higher requirements for intelligent, functional and miniaturized devices. Smart wearable fabrics have also become the research object that scholars from all over the world are happy to study, and the demand market is gradually expanding. The research and development of smart wearable fabrics meets people's needs for different functions such as sensing, energy storage, thermal management, color change and luminescence. Among them, luminous fabrics also have important and extensive application value in the fields of display, communication and intelligent robots. Common luminescent materials include photoluminescence, electroluminescence, ray luminescence, thermoluminescence, photoluminescence and radioluminescence. Among them, electroluminescence is a phenomenon that makes materials emit light under the action of DC or AC electric field, which belongs to the electrically controlled luminescence method. Therefore, electroluminescent fibers and their fabrics have the advantages of fast response speed, high brightness, easy processing and easy control.
[0003] There are many processes for preparing electroluminescent fibers at present. For example, Chinese invention patent CN108093535A discloses a method for preparing highly elastic electroluminescent fibers. The method designs a multi-channel parallel extrusion needle, and extrudes a fiber structure of two parallel hydrogel electrodes wrapped with a luminescent active layer. However, since the maximum luminous intensity point of the structure is located in the central area of the fiber, the brightness of the fiber will be attenuated to a certain extent, and the selection of the substrate material used is also limited. The hydrogel electrode is greatly affected by the environment, and the cost is high, making it difficult to achieve batch production; Chinese invention patent CN1427652A discloses a method for preparing electroluminescent fibers. From the inside to the outside, it includes a central electrode, a dielectric insulating layer, a luminescent layer, a transparent electrode and an auxiliary electrode, an anti-aging filler and a protective sleeve, etc. The dielectric layer and the luminescent layer are both prepared by a dip-coating and stretching method, and the transparent electrode is prepared by a reactive evaporation method. The preparation process is complex and costly, making it difficult to achieve mass production. Chinese invention patent CN107275498 A discloses a flexible electroluminescent device and a method for preparing the same, which includes a conductive nanofiber bundle, a light-emitting layer coated on the surface of the conductive nanofiber bundle, and a transparent conductive film coated on the surface of the light-emitting layer. The transparent conductive film involves processes such as electroplating and vapor deposition, and has a high preparation cost and is difficult to mass produce.
[0004] Chinese invention patent CN108505187A discloses a luminous fabric and a preparation method thereof. The method loads luminescent active materials on the outside of a flexible fiber conductor to obtain conductive luminescent active fibers, assembles the conductive luminescent active fibers with conductive fibers, and finally packages them. This method has a complex process and is not a one-step molding process, which creates difficulties for mass production. The use of electrospinning to prepare flexible electroluminescent fibers is also a common method at present. Chinese invention patent CN106883852A discloses a method using polyvinyl pyrrolidone (PVP) as a fiber-forming material, NN dimethylformamide as a solvent, tetrabutyl titanate, tetraethyl orthosilicate and Er nitrate as main raw materials. The electrospinning method is easy to prepare a precursor, and then the precursor fiber is dried and calcined to obtain a rare earth erbium-doped titanium dioxide / silicon dioxide composite nanofiber. This method has limited its application and development to a certain extent due to its complex steps. In addition, introducing an in-situ polymerization method to prepare luminescent raw materials is also a mature method currently developed. Chinese patent CN1234925C discloses a long afterglow luminescent polyamide fiber and a preparation method thereof, wherein the long afterglow luminescent polyamide fiber is composed of a polyamide fiber and a luminescent effective amount of Eu 2+ The composition of activated alkali metal aluminate, and its brief preparation method is as follows: prepare luminescent polyamide as raw material by in-situ polymerization method, directly melt-spin or blend with polyamide and then spin in a conventional way, and the desired long afterglow luminescent polyamide fiber can be obtained. The disadvantages of this method are that there are many preparation steps and the preparation process is relatively complicated. In China, invention patent CN104674539B discloses a method with simple preparation process and strong operability. This method uses sol-gel method to prepare strontium aluminate luminescent powder co-doped with europium and dysprosium with good luminescent performance, and deposits a uniform and dense luminescent layer on the surface of fiber and fabric by radio frequency magnetron sputtering technology, but the sol-gel method used in this method requires low temperature or mild preparation conditions, and this production method is also limited. Therefore, there is an urgent need for a method with simple preparation process and mass production, and at the same time, it is also necessary to have many characteristics such as controllable wire diameter and controllable structure in the process of preparing fibers, so as to meet the market demand for electroluminescent fibers. Summary of the invention
[0005] In order to solve the problems in the prior art, the present invention provides an electroluminescent fiber, which has a simple structure and reliable performance, and the optimization scheme can realize different colors or color combinations separately or simultaneously. In addition, the present invention also provides a method for preparing the electroluminescent fiber, which has the advantages of low production cost, simple operation, easy batch preparation, controllable wire diameter, controllable structure, and environmental friendliness. In addition, the present invention uses the above-mentioned electroluminescent fiber to prepare electroluminescent yarn and electroluminescent fabric.
[0006] Specifically, the technical solution of the present invention is as follows:
[0007] 1. An electroluminescent fiber, comprising:
[0008] Two or more conductive layers; and,
[0009] A light emitting layer is disposed between the conductive layers.
[0010] 2. The electroluminescent fiber according to item 1, wherein the light-emitting layer contains a first polymer material and an electroluminescent material.
[0011] 3. The electroluminescent fiber according to item 1,
[0012] The first polymer material is selected from polymethyl methacrylate (PMMA), fluororesin, PMMA composite material doped with fluorinated polymer (F-PMMA), styrene dimethyl methacrylate copolymer (SMMA), cycloolefin copolymer (COC), cycloolefin polymer (COP), polycarbonate (PC), polyphenylene sulfone resin (PPSU), polyether sulfone resin (PES), polyethylene imine (PEI), polystyrene (PS), polyethylene (PE), polypropylene (PP), polyamide (PA), polyimide (PI), polyethylene terephthalate (PET), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), styrene-ethylene / butylene-styrene block copolymer (SEBS), polyurethane (PU), polyvinyl chloride (PVC), polystyrene (PS), polytrimethylene terephthalate (PTT), polyvinylidene chloride resin ( The present invention relates to a polyethylene terephthalate (PET) polymer, and the like. The present invention relates to a polyethylene terephthalate (PET) polymer, and the like. The present invention relates to a polyethylene terephthalate (PET) polymer, and the like. The present invention relates to a polyethylene terephthalate (PET) polymer, and the like.
[0013] 4. The electroluminescent fiber according to item 2,
[0014] The conductive layer comprises an inner conductive layer and an outer transparent conductive layer;
[0015] The inner conductive layer, the light emitting layer and the outer transparent conductive layer are arranged in sequence from the inside to the outside.
[0016] 5. According to the electroluminescent fiber described in item 4, the material of the outer transparent conductive layer includes electronic transparent conductive material and / or ionic transparent conductive material.
[0017] 6. The electroluminescent fiber according to item 5,
[0018] The electronic transparent conductive material is a conductive polymer or a polymer composite material;
[0019] The polymer composite material is a combination of one or more of a nano-scale inorganic non-metallic material, an inorganic metal material and a semiconductor material dispersed in a second polymer material; wherein,
[0020] The conductive polymer includes poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT / PSS);
[0021] The inorganic non-metallic material is selected from one or a combination of two or more of graphene, carbon nanotubes, carbon nanorods, and MXene;
[0022] The inorganic metal material is selected from one or a combination of two or more of nanosilver wires, nanogold wires, nanocopper wires, metal or oxide metal grids;
[0023] The semiconductor material is selected from one or a combination of two or more of indium tin oxide (ITO), antimony tin oxide (ATO), and zinc oxide (ZTO); and / or,
[0024] The ionic transparent conductive material is a transparent solid polymer electrolyte, which is a lithium salt dissolved in a third polymer material. The lithium salt is selected from one or a combination of two or more of lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium perchlorate (LiClO4), lithium tetrafluoroarsenate (LiAsF4) and lithium tetrafluoroborate (LiBF4).
[0025] 7. According to the electroluminescent fiber described in item 6, the second polymer material and the third polymer material are transparent thermoplastic polymer materials, selected from one or a combination of two or more of polymethyl methacrylate (PMMA), fluororesin, fluororesin-modified polymethyl methacrylate (F-PMMA), cycloolefin copolymer (COC), polyvinylidene fluoride (PVDF), polystyrene (PS), polycarbonate (PC), styrene dimethyl methacrylate copolymer (SMMA), cycloolefin polymer (COP), and styrene-ethylene / butylene-styrene block copolymer (SEBS).
[0026] 8. According to the electroluminescent fiber described in item 2, two or more conductive layers are arranged in the light-emitting layer. Preferably, the conductive layers are conductive fibers. Further preferably, the two or more conductive layers are arranged parallel to each other.
[0027] 9. The electroluminescent fiber according to item 8,
[0028] The light-emitting layer comprises two or more light-emitting layer units arranged along the axial direction of the electroluminescent fiber;
[0029] The electroluminescent materials between at least one of the light-emitting layer units and other light-emitting layer units have different light-emitting bands;
[0030] The conductive layer is in contact with at least one light-emitting layer unit.
[0031] 10. The electroluminescent fiber according to item 8 or 9,
[0032] The conductive wire is a metal wire, and its outer surface is distributed with uneven defects, and / or its outer surface is coated with a dielectric insulation layer with a high dielectric constant;
[0033] Preferably, the dielectric insulating layer material with a high dielectric constant is selected from one of barium titanate (BaTiO3), lead titanate (PbTiO3), strontium titanate (SrTiO3), titanium dioxide (TiO2), or a nano-coating of a combination of two or more thereof.
[0034] 11. The electroluminescent fiber according to any one of items 1 to 10, wherein the outermost layer of the electroluminescent fiber is coated with a transparent protective layer, and the transparent protective layer is preferably a fourth polymer material.
[0035] 12. The electroluminescent fiber according to item 11,
[0036] The fourth polymer material is a transparent thermoplastic polymer material, selected from one or more of polymethyl methacrylate (PMMA), fluororesin, fluororesin-modified polymethyl methacrylate (F-PMMA), cycloolefin copolymer (COC), polyvinylidene fluoride (PVDF), polystyrene (PS), polycarbonate (PC), styrene dimethyl methacrylate copolymer (SMMA), cycloolefin polymer (COP), and styrene-ethylene / butylene-styrene block copolymer (SEBS).
[0037] 13. According to the electroluminescent fiber described in item 12, functional materials are added to the transparent protective layer, and the functional materials are evenly distributed in the transparent protective layer.
[0038] 14. The electroluminescent fiber according to item 13,
[0039] The functional material is selected from one or a combination of two or more of a photoluminescent material, a fluorescent material, and a scattering agent;
[0040] Preferably, the scattering agent is selected from one or a combination of two or more of TiO2, BaSO4, Al2O3, MgO, BeO, Y2O3, ZrO2, GaAs, ZnS, ZnSe, MgF2, and CaF2.
[0041] 15. The electroluminescent fiber according to any one of items 2 to 14,
[0042] The mass percentage of the electroluminescent material in the light-emitting layer is 0.1wt.%-70wt.%, preferably 20wt.%-50wt.%; and / or,
[0043] The concentration distribution of the electroluminescent material in the luminescent layer remains constant or gradually decreases or increases from the inside to the outside of the fiber radial direction.
[0044] 16. The electroluminescent fiber according to any one of items 2 to 15,
[0045] The electroluminescent material is one or a combination of two or more of a sulfide system long afterglow material, alkaline earth metal sulfide, a sulfide material with rare earth as an activator, an aluminate system long afterglow material, a silicate system long afterglow material, a gallate system long afterglow material, a silicon-based oxynitride series, a stannate system, a phosphate system, a titanate system, a rare earth-doped or transition metal-doped up-conversion luminescent material, and a luminescent quantum dot.
[0046] 17. The electroluminescent fiber according to any one of item 16,
[0047] The long afterglow material of the sulfide system includes transition metal sulfides, wherein the transition metal sulfides are selected from ZnS:Cu 2+ 、ZnS:Mn 2+ 、ZnS:Cu 2+ ,Co 2+ One or a combination of two or more of the following: and / or
[0048] Alkaline earth metal sulfide selected from CaS:Cu 2+ 、CaS:Ba 3+ 、CaSrS:Ba 3+ One or a combination of two or more of the following: and / or
[0049] The rare earth sulfide material used as the activator is selected from Y2O2S:Eu 3+ Mg 2+ ,Ti 4+ 、CaS:Eu 2+ ,Pr3+ 、CaS:Eu 2+ ,Tm 3+ One or a combination of two or more of the following: and / or
[0050] The long afterglow material of the aluminate system is selected from CaAl2O4:Eu 2+ ,Nd 3+ 、Sr3Al2O4:Eu 2+ ,Dy 3+ 、Sr4Al 14 O 25 :Eu 2+ ,Dy 3+ 、CaAl4O7:Ce 3+ 、MAlO3:Mn 4+ ,Ge 4+ (M=La, Gd) or a combination of two or more thereof; and / or,
[0051] The long afterglow material of the silicate system is selected from MgSiO3:Mn 2+ ,Eu 2+ ,Dy 3+ 、CdSiO3:Mn 2+ 、CdSiO3:Sm 2+ 、Ba2ZrSi3O9:Eu 2+ ,Pr 3+ One or a combination of two or more of the following: and / or
[0052] The long afterglow material of the gallate (gallium germanate) system is selected from ZnGa2O4:Cr 3+ 、Zn3Ga2Ge2O 10 :Cr 3+ 、Zn2Ga2Ge2O 10 :Cr 3+ ,Pr 3+ 、Mg4Ga8Ge2O 20 :Cr 3+ One or a combination of two or more of the following: and / or
[0053] Silicon-based oxynitride series include LaSi3N5:Ce 3+ and / or,
[0054] The stannate system is selected from Sr2SnO4:Sm 3+ or CaSnO3:Pr 3+ and / or,
[0055] Titanate systems include CaTiO3:Pr 3+ and / or,
[0056] The up-conversion luminescent material is selected from one or a combination of two or more nanocrystals of NaYF4, NaGdF4, LiYF4, YF3, CaF2 fluoride or Gd2O3 oxide; such as NaYF4:Er, Yb, etc. and / or,
[0057] The light-emitting quantum dots are selected from one or a combination of two or more of cadmium sulfide (CdS), cadmium selenide (CdSe), and cadmium telluride (CdTe).
[0058] 18. The electroluminescent fiber according to any one of items 1 to 17,
[0059] The cross section of the electroluminescent fiber is one of a circle, a triangle, a rectangle, an ellipse and a five-pointed star.
[0060] 19. A method for preparing an electroluminescent fiber, comprising the following steps:
[0061] Compounding a first polymer material and an electroluminescent material to prepare an electroluminescent composite material;
[0062] A transparent conductive material and an electroluminescent composite material are prepared into a preform, wherein the transparent conductive material is located in the cladding layer of the preform, the electroluminescent composite material is located in the core layer of the preform, and a hole structure is arranged in the electroluminescent composite material located in the core layer along the axial direction of the preform;
[0063] The conductive layer is passed through the hole structure of the preform rod, and a composite structure fiber with a light-emitting layer and a conductive layer is prepared by heat softening and drawing.
[0064] 20. The preparation method according to item 19,
[0065] The transparent conductive material includes an electronic transparent conductive material and / or an ionic transparent conductive material.
[0066] 21. The preparation method according to item 20,
[0067] The electronic transparent conductive material is a conductive polymer or a polymer composite material;
[0068] The polymer composite material is a combination of one or more of a nano-scale inorganic non-metallic material, an inorganic metal material and a semiconductor material dispersed in a second polymer material; wherein,
[0069] The conductive polymer includes poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT / PSS);
[0070] The inorganic non-metallic material is selected from one or a combination of two or more of graphene, carbon nanotubes, carbon nanorods, and MXene;
[0071] The inorganic metal material is selected from one or a combination of two or more of nano silver wires / gold wires / copper wires, metal materials such as silver or copper, or oxide metal grids;
[0072] The semiconductor material is one or a combination of two or more selected from indium tin oxide (ITO), antimony tin oxide (ATO), zinc oxide (ZTO); and / or,
[0073] The ionic transparent conductive material is a transparent solid polymer electrolyte, which is a lithium salt dissolved in the third polymer material, and the lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium perchlorate (LiClO4), lithium tetrafluoroarsenate (LiAsF4) and lithium tetrafluoroborate (LiBF4).
[0074] 22. The preparation method according to item 21,
[0075] The second polymer material and the third polymer material are transparent thermoplastic polymer materials, selected from one or more of polymethyl methacrylate (PMMA), fluororesin, fluororesin-modified polymethyl methacrylate (F-PMMA), cycloolefin copolymer (COC), polyvinylidene fluoride (PVDF), polystyrene (PS), polycarbonate (PC), styrene dimethyl methacrylate copolymer (SMMA), cycloolefin polymer (COP), and styrene-ethylene / butylene-styrene block copolymer (SEBS).
[0076] 23. A method for preparing an electroluminescent fiber, comprising the following steps:
[0077] Compounding a first polymer material and an electroluminescent material to prepare an electroluminescent composite material;
[0078] The electroluminescent composite material is prepared into a preform, wherein the preform is provided with a hole structure along the axial direction thereof, wherein the hole structure comprises more than two holes along the axial direction of the preform, and preferably, the more than two holes are parallel to each other;
[0079] Passing the conductive layers through two or more holes of the preform rod respectively, and preparing and obtaining the electroluminescent fiber by a heat softening wire drawing method;
[0080] Preferably, the conductive layer is a conductive thread.
[0081] 24. The preparation method according to item 23,
[0082] The preform rod is composed of two or more electroluminescent composite materials arranged along its axial direction, and the luminescent materials of at least one of the electroluminescent composite materials have different luminescent wavelength bands from those of the other electroluminescent composite materials;
[0083] The hole is in contact with at least one of the electroluminescent composite materials.
[0084] 25. The preparation method according to item 23,
[0085] The conductive wire is a metal wire, and its outer surface is distributed with uneven defects, and / or its outer surface is coated with a dielectric insulating layer with a high dielectric constant;
[0086] Preferably, the material of the high dielectric constant dielectric insulating layer is a nano-coating selected from one or a combination of two or more of barium titanate (BaTiO3), lead titanate (PbTiO3), strontium titanate (SrTiO3), and titanium dioxide (TiO2).
[0087] 26. The preparation method according to any one of items 19 to 25,
[0088] The outer jacket of the preform rod is provided with a transparent material;
[0089] Preferably, the transparent material is a fourth polymer material; more preferably, a functional material is added to the transparent material.
[0090] 27. The preparation method according to item 26,
[0091] The fourth polymer material is a transparent thermoplastic polymer material, selected from one or more of polymethyl methacrylate (PMMA), fluororesin, fluororesin-modified polymethyl methacrylate (F-PMMA), cycloolefin copolymer (COC), polyvinylidene fluoride (PVDF), polystyrene (PS), polycarbonate (PC), styrene dimethyl methacrylate copolymer (SMMA), cycloolefin polymer (COP), and styrene-ethylene / butylene-styrene block copolymer (SEBS).
[0092] 28. The preparation method according to item 26,
[0093] The functional material is selected from one or a combination of two or more of a photoluminescent material, a fluorescent material, and a scattering agent;
[0094] Preferably, the scattering agent is selected from one or a combination of two or more of TiO2, BaSO4, Al2O3, MgO, BeO, Y2O3, ZrO2, GaAs, ZnS, ZnSe, MgF2, and CaF2.
[0095] 29. The preparation method according to any one of items 19 to 28,
[0096] The electroluminescent composite material is prepared by physical blending, physical / chemical blending or solution blending.
[0097] 30. The preparation method according to any one of items 19 to 29,
[0098] The electroluminescent material accounts for 0.1 wt.% to 70 wt.% by weight in the electroluminescent composite material, and preferably 20 wt.% to 50 wt.%.
[0099] 31. The preparation method according to any one of items 19 to 30,
[0100] The concentration distribution of the electroluminescent material in the electroluminescent composite material remains constant or gradually decreases or increases from the inside to the outside of the preform along the radial direction.
[0101] 32. The preparation method according to any one of items 19 to 31,
[0102] The first polymer material is selected from the group consisting of polymethyl methacrylate (PMMA), fluororesin, PMMA composite material doped with fluorinated polymer (F-PMMA), styrene dimethyl methacrylate copolymer (SMMA), cycloolefin copolymer (COC), cycloolefin polymer (COP), polycarbonate (PC), polyphenylene sulfone resin (PPSU), polyethersulfone resin (PES), polyethylene imine (PEI), polystyrene (PS), polyethylene (PE), polypropylene (PP), polyamide (PA), polyimide (PI), polyethylene terephthalate (PET), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), styrene-ethylene / butylene-styrene block copolymer (SEBS), polyurethane (PU), polyvinyl chloride (PVC), polystyrene (PS), polytrimethylene terephthalate (PTT), polyvinylidene chloride resin (PVDC), acrylonitrile-butadiene-styrene copolymer (ABS), polyethylene glycol (PEG), thermoplastic elastomer (TPE), low-density polyethylene (LDPE), polyethylene glycol (PEG), high-density polyethylene (HDPE), polyoxymethylene (POM), polyphenylene ether (PPO), polyester and sodium isophthalate sulfonate copolymer, acrylate copolymer, vinyl acetate resin, polyvinyl acetal, one or a combination of two or more thereof, preferably polymethyl methacrylate (PMMA), fluororesin, fluororesin-modified polymethyl methacrylate (F-PMMA), cycloolefin copolymer (COC), polyvinylidene fluoride (PVDF), polystyrene (PS), polycarbonate (PC), styrene dimethyl methacrylate copolymer (SMMA), cycloolefin polymer (COP), styrene-ethylene / butylene-styrene block copolymer (SEBS), one or a combination of two or more thereof.
[0103] 33. The preparation method according to any one of items 19 to 32,
[0104] The cross section of the electroluminescent fiber is one of a circle, a triangle, a rectangle, an ellipse and a five-pointed star.
[0105] 34. An electroluminescent yarn, said electroluminescent yarn being made by twisting two or more electroluminescent fibers;
[0106] The electroluminescent fiber is selected from any one or more electroluminescent fibers in items 1 to 18; and / or,
[0107] The electroluminescent fiber is selected from any one method in items 19 to 33 or electroluminescent fibers prepared by two or more methods respectively.
[0108] 35. An electroluminescent fabric,
[0109] The electroluminescent fabric contains electroluminescent fibers and / or electroluminescent yarns; or,
[0110] The electroluminescent fabric contains transparent conductive fibers and electroluminescent fibers and / or electroluminescent yarns;
[0111] Wherein, the electroluminescent fiber is selected from any one or more electroluminescent fibers in items 1 to 18; and / or, the electroluminescent fiber is selected from electroluminescent fibers prepared by any one or more methods in items 19 to 33;
[0112] The electroluminescent yarn is the electroluminescent yarn described in item 34.
[0113] The electroluminescent fiber involved in the present invention has many characteristics such as simple structure, simple preparation method, batch production, controllable wire diameter, unique structure, etc. The electroluminescent fiber has good luminous effect, the combination of the luminescent layer and the conductive layer is firm, and the multi-electrode luminescent fiber can be prepared by controlling the number and distribution of holes. The multi-electrode luminescent fiber can control the luminous effect more accurately and stably, and can also regulate the color of the electrochromic fiber (such as monochrome electroluminescent fiber, two-color electroluminescent fiber, three-color electroluminescent fiber). In addition, it can be further woven into a fabric, and it is not easy to be damaged in a bent and folded state, and has the characteristics of excellent wearability and luminous effect. In the future, the electroluminescent fiber can also be widely used in clothing, decoration, industry, fishery, transportation and other fields.
[0114] The above description is only an overview of the technical solution of the present invention. In order to make the technical means of the present invention clearer and to enable those skilled in the art to implement it according to the contents of the specification, and to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described below by way of example. BRIEF DESCRIPTION OF THE DRAWINGS
[0115] Figure 1 : is a schematic diagram of the structure of the first electroluminescent fiber in the present invention;
[0116] Figure 2 : is a schematic diagram of the structure of the second electroluminescent fiber in the present invention;
[0117] Figure 3 : is a schematic diagram of the structure of the third electroluminescent fiber in the present invention;
[0118] Figure 4 : is a schematic diagram of the structure of the fourth electroluminescent fiber in the present invention;
[0119] Figure 5 : is a schematic diagram of the structure of the fifth electroluminescent fiber in the present invention;
[0120] Figure 6 : is a schematic diagram of the sixth electroluminescent fiber structure of the present invention;
[0121] Figure 7 : is a schematic diagram of the seventh electroluminescent fiber structure of the present invention;
[0122] Figure 8 : is a schematic diagram of the structure of the eighth electroluminescent fiber in the present invention;
[0123] Fig. 9 : is a schematic diagram of the ninth electroluminescent fiber structure of the present invention;
[0124] Fig.10 : is a schematic diagram of the structure of the tenth electroluminescent fiber in the present invention;
[0125] Fig.11 : Schematic diagram of electroluminescent fabric;
[0126] Fig.12 : is a schematic diagram of the fiber preparation process of the present invention;
[0127] Fig.13 : This is a test diagram of the visible-ultraviolet fiber spectrometer of the electroluminescent fiber of Example 12 of the present invention.
[0128] Figure numerals: 1. conductive layer; 2. light-emitting layer; 3. outer transparent conductive layer; 4. outer transparent protective layer; 5. coil; 6. rod feeding device; 7. preform rod; 8. heating furnace; 9. diameter gauge; 10. coating device; 11. auxiliary traction; 12. wire taking-up. DETAILED DESCRIPTION
[0129] The following embodiments of the present invention are only used to illustrate the specific embodiments of the present invention, and these embodiments cannot be understood as limiting the present invention. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention are regarded as equivalent replacement methods and fall within the scope of protection of the present invention.
[0130] The following are related implementations of the electroluminescent fiber.
[0131] In a specific embodiment, an electroluminescent fiber is disclosed, comprising: two or more conductive layers; and a light-emitting layer disposed between the conductive layers.
[0132] The electroluminescent fiber provided in this embodiment has a simple structure and stable performance.
[0133] It should be noted that the "conductive layer" in the present invention is not just a layered or sheet-like structure. As long as an electric field can be formed between the conductive layers, the cross-section of the conductive layer can be any shape such as a circle or a polygon.
[0134] Likewise, the light-emitting layer is not limited to a layered or thin sheet structure, and its cross section may be of any shape as long as it emits light in an electric field between two or more conductive layers.
[0135] In a specific embodiment, the conductive layer is conductive wire.
[0136] This embodiment provides a specific conductive layer, which is a conductive thread.
[0137] In one embodiment, the light-emitting layer contains a polymer material and an electroluminescent material.
[0138] This embodiment provides a specific structure of the light-emitting layer, the material of which is an electroluminescent composite material, specifically an electroluminescent composite material obtained by compounding a first polymer material with an electroluminescent material.
[0139] In the present invention, the electroluminescent material refers to a material that directly converts electrical energy into light energy under the action of a direct current or alternating current electric field by relying on the excitation of the current and the electric field.
[0140] In a specific embodiment, the first polymer material is selected from polymethyl methacrylate (PMMA), fluororesin, PMMA composite material doped with fluorinated polymer (F-PMMA), styrene dimethyl methacrylate copolymer (SMMA), cycloolefin copolymer (COC), cycloolefin polymer (COP), polycarbonate (PC), polyphenylene sulfone resin (PPSU), polyether sulfone resin (PES), polyethylene imine (PEI), polystyrene (PS), polyethylene (PE), polypropylene (PP), polyamide (PA), polyimide (PI), polyethylene terephthalate (PET), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), styrene-ethylene / butylene-styrene block copolymer (SEBS), polyurethane (PU), polyvinyl chloride (PVC), polystyrene (PS), polytrimethylene terephthalate (PTT), polyvinylidene terephthalate (PTT), polyvinyl chloride (PVC), polystyrene (PS), polytrimethylene ...PS), polytrimethylene terephthalate (PS), polyvinyl chloride (PVC), polystyrene (PS), polytrimethylene terephthalate (PTT), polyvinyl chloride The invention can be selected from the group consisting of polyvinyl chloride resin (PVDC), acrylonitrile-butadiene-styrene copolymer (ABS), polyethylene glycol (PEG), thermoplastic elastomer (TPE), low-density polyethylene (LDPE), polyethylene glycol (PEG), high-density polyethylene (HDPE), polyoxymethylene (POM), polyphenylene oxide (PPO), polyester and sodium isophthalate sulfonate copolymer, acrylate copolymer, vinyl acetate resin, and polyvinyl acetal, and preferably selected from the group consisting of polymethyl methacrylate (PMMA), fluororesin, fluororesin-modified polymethyl methacrylate (F-PMMA), cycloolefin copolymer (COC), polyvinylidene fluoride (PVDF), polystyrene (PS), polycarbonate (PC), styrene dimethyl methacrylate copolymer (SMMA), cycloolefin polymer (COP), and styrene-ethylene / butylene-styrene block copolymer (SEBS).
[0141] In this embodiment, specific types of the first polymer material are given.
[0142] In a specific embodiment, Figure 1 As shown, the conductive layer includes an inner conductive layer and an outer transparent conductive layer 3;
[0143] The (inner) conductive layer 1, the light-emitting layer 2, and the outer transparent conductive layer 3 are arranged in sequence from the inside to the outside.
[0144] This embodiment provides an electroluminescent fiber, which can be specifically Figure 1 As shown, the conductive layer is divided into an (inner) conductive layer 1 and an outer transparent conductive layer 3, which form an electric field to make the light-emitting layer 2 emit light, and the emitted light is emitted through the outer transparent conductive layer 3.
[0145] In a specific embodiment, the material of the outer transparent conductive layer 3 includes electronic transparent conductive material and / or ionic transparent conductive material.
[0146] This embodiment provides specific materials for the outer transparent conductive layer.
[0147] In the present invention, the electronic transparent conductive material refers to a transparent polymer material in which the first type of conductive material is distributed, wherein a large number of freely movable electrons exist. Under the action of an external electric field, the electrons move in a directional manner to form an obvious current.
[0148] In the present invention, the ionic transparent conductive material refers to a transparent polymer material distributed with a second type of conductive material, in which a large number of freely movable ions exist, and the ions perform directed diffusion movement under the action of an electric field.
[0149] In one embodiment, the electronically transparent conductive material is a conductive polymer or a polymer composite material;
[0150] The polymer composite material is a combination of one or more of a nano-scale inorganic non-metallic material, an inorganic metal material and a semiconductor material dispersed in a second polymer material; wherein,
[0151] The conductive polymer includes poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT / PSS);
[0152] The inorganic non-metallic material is selected from one or a combination of two or more of graphene, carbon nanotubes, carbon nanorods, and MXene;
[0153] The inorganic metal material is selected from one or a combination of two or more metal materials such as nanosilver wire, nanogold wire, nanocopper wire, or metal grid;
[0154] The semiconductor material is selected from one or a combination of two or more of indium tin oxide (ITO), antimony tin oxide (ATO), and zinc oxide (ZTO).
[0155] In the present invention, the metal grid refers to: threads of conductive metals such as gold, silver or copper and their oxides densely distributed on a transparent polymer substrate to form a conductive network with a regular shape.
[0156] In addition, since inorganic non-metallic materials, metal materials and semiconductor materials are not transparent materials, they are dispersed in polymer materials to obtain the outer transparent conductive layer 3.
[0157] This embodiment provides a specific electronic transparent conductive material.
[0158] In a specific embodiment, the ionic transparent conductive material is a transparent solid polymer electrolyte, which is a lithium salt dissolved in a third polymer material, and the lithium salt is selected from one or a combination of two or more of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium tetrafluoroarsenate (LiAsF4) and lithium tetrafluoroborate (LiBF4).
[0159] This embodiment provides a specific ionic transparent conductive material.
[0160] In a specific embodiment, the second polymer material and the third polymer material are transparent thermoplastic polymer materials, selected from one or a combination of two or more of polymethyl methacrylate (PMMA), fluororesin, polymethyl methacrylate modified by fluororesin (F-PMMA), cycloolefin copolymer (COC), polyvinylidene fluoride (PVDF), polystyrene (PS), polycarbonate (PC), styrene dimethyl methacrylate copolymer (SMMA), cycloolefin polymer (COP), and styrene-ethylene / butylene-styrene block copolymer (SEBS). This embodiment provides specific second polymer materials and third polymer materials.
[0161] In a specific embodiment, Figure 2-10 As shown, two or more conductive layers are arranged in the light-emitting layer along the axial direction of the electroluminescent fiber. Preferably, the conductive layer is a conductive wire. Further preferably, the two or more conductive layers are arranged parallel to each other.
[0162] This embodiment provides another structure of electroluminescent fiber.
[0163] Specifically, the light-emitting layer may include: a pair of conductive layers 1 (such as Figure 2 ); or, the light-emitting layer includes three conductive layers 1 (such as Figure 3 , 5 ); or, the light-emitting layer includes three conductive layers 1 arranged in parallel on the same plane (such as Figure 4 ); or, the light-emitting layer includes four conductive layers 1 (such as Figures 6 to 9 ); or, the light-emitting layer comprises four conductive layers, one of which is at the center of the light-emitting layer, and the other three conductive layers are evenly distributed around the central conductive layer (such as Fig.10 , that is, on the fiber cross section, three conductive layers are distributed in an equilateral triangle, and another conductive layer is located at the center of the equilateral triangle).
[0164] In addition, as mentioned above Figure 2-Figure 10In the technical solution, the two ends of the electroluminescent fiber can be rotated in opposite directions along the circumference of the electroluminescent fiber, so that the two or more conductive layers are spiral-shaped, and the above technical effects can still be achieved. In short, the two or more conductive layers do not intersect in the light-emitting layer, so that an electric field can be formed between the two or more conductive layers.
[0165] In this embodiment, an electric field is formed between two or more conductive layers 1 , so that the light-emitting layer 2 wrapping the conductive layer 1 emits light, and the emitted light is directly emitted from the light-emitting layer 2 .
[0166] In a specific embodiment, the light-emitting layer includes two or more light-emitting layer units (such as Figures 4 to 10 In the figure, light-emitting layer units of different color depths represent different light-emitting layer units, and more than two light-emitting layer units together constitute the light-emitting layer 2);
[0167] The electroluminescent materials between at least one of the light-emitting layer units and other light-emitting layer units have different light-emitting bands;
[0168] The conductive layer is in contact with at least one light-emitting layer unit.
[0169] like Figure 4 , Figure 5 , Fig.10 In the electroluminescent fiber shown in , at least one conductive layer 1 is in contact with each light-emitting unit at the same time, and the other conductive layers are inside each light-emitting unit.
[0170] like Figure 4 , Figure 5 As shown, it specifically includes two light-emitting units and three conductive layers, one conductive layer is located at the interface of the two light-emitting units, and the other two conductive layers are located in the two light-emitting units. When an electric field is formed between the middle conductive wire and any other conductive wire, different colors of light can be emitted respectively, or an electric field can be formed between the three conductive wires to emit different lights at the same time, or an electric field can be formed between different conductive wires alternately to emit different lights alternately.
[0171] Similarly, if Fig.10 The electroluminescent fiber shown in the figure specifically includes three light-emitting units and four conductive layers, wherein one conductive layer is located at the junction of the three light-emitting units, and the other three conductive layers are located in the three light-emitting units respectively. An electric field can be formed between the conductive layer in the middle and other conductive layers or other conductive layers, thereby realizing mixed light emission of two or more colors; of course, the above combinations can also be used alternately to emit different lights alternately.
[0172] like Figure 6 , Figure 7In the electroluminescent fiber shown, the conductive layer can be located at the interface between the light-emitting unit and the outer transparent protective layer 4, as long as an electric field can be formed between the conductive layers to make the electroluminescent composite material emit light.
[0173] In addition, in electroluminescent fibers, the conductive fibers are located at the interface between the two light-emitting units. Figure 8 , Fig. 9 In the figure, the light-emitting units located on the upper and lower sides are the same type of light-emitting units. When an electric field is formed between different conductive wires, different colors of light can be emitted respectively; or an electric field can be formed between all four conductive wires, thereby emitting different lights at the same time; of course, the above combinations can also be used alternately to emit different lights alternately.
[0174] Therefore, this embodiment is a further improvement on the previous embodiment, and can make the conductive layers on both sides of different types of light-emitting units conductive, and can form different colors of light respectively; of course, different conductive wires can be arbitrarily combined to form an electric field or all conductive wires can form an electric field, so that different combinations form different colors or different color combinations of light; or, the combination can be continuously changed, so that different colors of light can be flashed. In this way, the electroluminescent fiber of the present invention can show different colors, different color combinations, and different colors or color combinations that emit light alternately, so that the electroluminescent fiber of the present invention can be applied to more scenes, expanding the application range of the electroluminescent fiber of the present invention.
[0175] In a specific embodiment, Figure 1-10 As shown, the conductive wire is a metal wire with uneven defects distributed on its surface. In this embodiment, the uneven defects distributed on the surface of the metal wire can make the conductive layer 1 and the light-emitting layer 2 contact more closely, thereby increasing the adhesion between the two.
[0176] In a specific embodiment, Figure 1-10 As shown, the conductive wire is a metal wire, and its surface is coated with a dielectric insulating layer with a high dielectric constant (generally refers to relative dielectric constant, and relative dielectric constant has no unit); preferably, the dielectric insulating layer material with a high dielectric constant is selected from a nano coating containing one or a combination of two or more of barium titanate (BaTiO3), lead titanate (PbTiO3), strontium titanate (SrTiO3), and titanium dioxide (TiO2). In the present invention, a high dielectric constant refers to a material or composite material with a dielectric constant greater than 10, which will generate induced charges and weaken the electric field when an external electric field is applied. By coating the metal wire surface with a dielectric insulating layer with a high dielectric constant, the light-emitting layer can be prevented from being electrically broken down and fluorescence quenching.
[0177] In a specific embodiment, the light-emitting layer is further coated with a transparent protective layer, and the transparent protective layer is preferably a fourth polymer material.
[0178] In a specific embodiment, the fourth polymer material is a transparent thermoplastic polymer material, selected from one or more of polymethyl methacrylate (PMMA), fluororesin, fluororesin-modified polymethyl methacrylate (F-PMMA), cycloolefin copolymer (COC), polyvinylidene fluoride (PVDF), polystyrene (PS), polycarbonate (PC), styrene dimethyl methacrylate copolymer (SMMA), cycloolefin polymer (COP), and styrene-ethylene / butylene-styrene block copolymer (SEBS).
[0179] This embodiment provides a specific fourth polymer material.
[0180] By providing a transparent protective layer on the surface of the electroluminescent fiber, the electroluminescent fiber can be made more durable. The outer transparent protective layer can effectively prevent the electroluminescent material of the light-emitting layer from deliquescing and becoming ineffective, and also prevent electric shock when people touch it.
[0181] In a specific embodiment, functional materials are added into the transparent protective layer, and the functional materials are evenly distributed in the transparent protective layer.
[0182] In the present invention, functional materials refer to materials that have specific functions after being acted upon by light, electricity, magnetism, heat, chemistry, biochemistry, etc., especially materials that can emit light or change the reflection angle of light to scatter light under light stimulation.
[0183] Adding functional materials into the transparent protective layer can make the transparent protective layer have the functions of the corresponding functional materials.
[0184] In a specific embodiment, the functional material is selected from one or a combination of two or more of a photoluminescent material, a fluorescent material, and a scattering agent;
[0185] Preferably, the scattering agent is selected from one or a combination of two or more of TiO2, BaSO4, Al2O3, MgO, BeO, Y2O3, ZrO2, GaAs, ZnS, ZnSe, MgF2, and CaF2.
[0186] In the present invention, photoluminescent material refers to a material that can emit light when excited by ultraviolet light, visible light, etc. Adding photoluminescent material to the transparent protective layer can adjust the luminescent spectrum and luminescent brightness of the electroluminescent fiber (low-energy light excitation, high-energy light emission).
[0187] In the present invention, the fluorescent material refers to a material that absorbs light of a certain wavelength and immediately emits light of a different wavelength. When the incident light disappears, the fluorescent material immediately stops emitting light. Adding the fluorescent material to the transparent protective layer can adjust the luminous spectrum of the electroluminescent fiber, thereby broadening the spectrum within a limited electroluminescent spectrum range.
[0188] In the present invention, the scattering agent refers to a material that can cause light to radiate in all directions (when a light beam passes through an inhomogeneous medium, part of the light beam will deviate from the original direction and spread in a dispersed manner). Adding a scattering agent to the transparent protective layer can adjust the light scattering angle of the electroluminescent fiber, making the light emission more uniform and soft.
[0189] In a specific embodiment, the mass proportion of the electroluminescent material in the light-emitting layer is 0.1wt.% to 70wt.%, specifically 0.1wt.%, 1wt.%, 5wt.%, 10wt.%, 20wt.%, 30wt.%, 40wt.%, 50wt.%, 60wt.%, 70wt.%; preferably 20wt.%-50wt.%.
[0190] In this embodiment, the mass ratio of the electroluminescent material in the light-emitting layer is 0.1wt.% to 70wt.%, within which the electroluminescent fiber can be prepared in batches and has excellent light-emitting performance. Above this range, the electroluminescent fiber is difficult to prepare, especially when the mass ratio is preferably 20wt.% to 50wt.%, the mechanical properties are relatively superior while ensuring its light-emitting performance. Below 20wt% concentration, the mechanical properties are good but the light-emitting performance is relatively poor, and above 50wt.% concentration, the light-emitting performance is good but the mechanical properties are relatively poor.
[0191] In a specific embodiment, the concentration distribution of the electroluminescent material in the luminescent layer remains constant or gradually decreases or increases from the inside to the outside of the fiber radial direction.
[0192] When the concentration distribution in the light-emitting layer remains constant from the inside to the outside along the radial direction of the fiber, batch preparation of electroluminescent fibers and excellent light-emitting properties can be achieved.
[0193] When the concentration distribution in the luminescent layer gradually increases along the radial direction of the fiber, the luminescent performance of the electroluminescent fiber can be achieved while taking into account its mechanical properties. Compared with the concentration remaining unchanged from the inside to the outside along the radial direction of the fiber (comparing the concentration of the outermost layer), the luminescent performance is slightly weakened, but the mechanical properties are significantly improved.
[0194] When the concentration distribution in the luminescent layer gradually decreases along the radial direction of the fiber, the luminescent performance of the electroluminescent fiber can be achieved while taking into account its mechanical properties. Compared with the concentration remaining unchanged from the inside to the outside along the radial direction of the fiber (comparing the concentration of the outermost layer), the mechanical properties are weakened but the luminescent performance is significantly improved.
[0195] In a specific embodiment, the electroluminescent material is a long afterglow material of a sulfide system, an alkaline earth metal sulfide, a sulfide material with a rare earth as an activator, a long afterglow material of an aluminate system, a long afterglow material of a silicate system, a long afterglow material of a gallate (gallium germanate) system, a long afterglow material of other systems such as a silicon-based oxynitride series, a stannate system, a phosphate system, a titanate system, a rare earth-doped or transition metal-doped upconversion luminescent material, and one or more of luminescent quantum dots.
[0196] The types of electroluminescent materials are given in this example.
[0197] In a specific embodiment, the long afterglow material of the sulfide system includes a transition metal sulfide, and the transition metal sulfide is selected from ZnS:Cu 2+ 、ZnS:Mn 2+ 、ZnS:Cu 2+ ,Co 2+ One or a combination of two or more of the following: and / or
[0198] Alkaline earth metal sulfide selected from CaS:Cu 2+ 、CaS:Ba 3+ 、CaSrS:Ba 3+ One or a combination of two or more of the following: and / or
[0199] The rare earth sulfide material used as the activator is selected from Y2O2S:Eu 3+ Mg 2+ ,Ti 4+ 、CaS:Eu 2+ ,Pr 3+ 、CaS:Eu 2+ ,Tm 3+ One or a combination of two or more of the following: and / or
[0200] The long afterglow material of the aluminate system is selected from CaAl2O4:Eu 2+ ,Nd 3+ 、Sr3Al2O4:Eu 2+ ,Dy 3+ 、Sr4Al 14 O 25 :Eu 2+ ,Dy 3+ 、CaAl4O7:Ce 3+ 、MAlO3:Mn 4+ ,Ge 4+ (M=La, Gd) or a combination of two or more thereof; and / or,
[0201] The long afterglow material of the silicate system is selected from MgSiO3:Mn2+ ,Eu 2+ ,Dy 3+ 、CdSiO3:Mn 2+ 、CdSiO3:Sm 2+ 、Ba2ZrSi3O9:Eu 2+ ,Pr 3+ One or a combination of two or more of the following: and / or
[0202] The long afterglow material of the gallate (gallium germanate) system is selected from ZnGa2O4:Cr 3+ 、Zn3Ga2Ge2O 10 :Cr 3+ 、Zn2Ga2Ge2O 10 :Cr 3+ ,Pr 3+ 、Mg4Ga8Ge2O 20 :Cr 3+ One or a combination of two or more of the following: and / or
[0203] Silicon-based oxynitride series include LaSi3N5:Ce 3+ and / or,
[0204] The stannate system is selected from Sr2SnO4:Sm 3+ or CaSnO3:Pr 3+ and / or,
[0205] Titanate systems include CaTiO3:Pr 3+ and / or,
[0206] The up-conversion luminescent material is selected from one or a combination of two or more nanocrystals of NaYF4, NaGdF4, LiYF4, YF3, CaF2 fluoride or Gd2O3 oxide; such as NaYF4:Er, Yb, etc. and / or,
[0207] The light-emitting quantum dots are selected from one or a combination of two or more of cadmium sulfide (CdS), cadmium selenide (CdSe), and cadmium telluride (CdTe).
[0208] Specific electroluminescent materials are given in this example.
[0209] In a specific embodiment, the cross-section of the electroluminescent fiber is one of a circle, a triangle, a rectangle, an ellipse, and a five-pointed star.
[0210] In this embodiment, several cross-sectional shapes of the electroluminescent fiber are listed. In addition, the electroluminescent fiber of the present invention only needs to be filamentous, and its cross-sectional shape is not limited to the above-listed shapes.
[0211] The following are related implementation methods of the method for preparing electroluminescent fibers.
[0212] In one embodiment, a method for preparing an electroluminescent fiber is disclosed, comprising the following steps:
[0213] Compounding a first polymer material and an electroluminescent material to prepare an electroluminescent composite material;
[0214] A transparent conductive material and an electroluminescent composite material are prepared into a preform, wherein the transparent conductive material is located in the cladding layer of the preform, the electroluminescent composite material is located in the core layer of the preform, and a hole structure is arranged in the electroluminescent composite material located in the core layer along the axial direction of the preform;
[0215] The conductive layer is passed through the hole structure of the preform rod, and the electroluminescent fiber is prepared by heat softening and drawing. This embodiment provides a method for preparing an electroluminescent fiber, wherein a conductive layer (specifically conductive wire in this embodiment) is passed through the hole structure of the preform rod prepared from the electroluminescent composite material, and then heat softening and drawing is performed, so that the electroluminescent fiber as shown in the attached figure can be prepared. Figure 1 The electroluminescent fiber has the same structure as the above. That is, the conductive filament forms the (inner) conductive layer 1, the transparent conductive material forms the outer transparent conductive layer 3, and the electroluminescent composite material forms the luminescent layer 2.
[0216] The method has the advantages of low production cost, simple operation, easy batch preparation, controllable wire diameter, controllable structure, and environmental friendliness.
[0217] In a specific embodiment, the transparent conductive material includes an electronic transparent conductive material and / or an ionic transparent conductive material.
[0218] In one embodiment, the electronically transparent conductive material is a conductive polymer or a polymer composite material;
[0219] The polymer composite material is a combination of one or more of a nano-scale inorganic non-metallic material, an inorganic metal material and a semiconductor material dispersed in a second polymer material; wherein,
[0220] The conductive polymer includes poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT / PSS);
[0221] The inorganic non-metallic material is selected from one or a combination of two or more of graphene, carbon nanotubes, carbon nanorods, and MXene;
[0222] The inorganic metal material is selected from one or a combination of two or more of nano silver wires / gold wires / copper wires, metal materials such as silver or copper, or oxide metal grids;
[0223] The semiconductor material is selected from one or a combination of two or more of indium tin oxide (ITO), antimony tin oxide (ATO), and zinc oxide (ZTO).
[0224] This embodiment lists several specific electronic transparent conductive materials.
[0225] In a specific embodiment, the ionic transparent conductive material is a transparent solid polymer electrolyte, which is a lithium salt dissolved in the third polymer material, and the lithium salt is selected from one or a combination of two or more of lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium perchlorate (LiClO4), lithium tetrafluoroarsenate (LiAsF4) and lithium tetrafluoroborate (LiBF4).
[0226] This embodiment lists several specific ionic transparent conductive materials.
[0227] In a specific embodiment, the second polymer material and the third polymer material are transparent thermoplastic polymer materials, selected from one or more of polymethyl methacrylate (PMMA), fluororesin, fluororesin-modified polymethyl methacrylate (F-PMMA), cycloolefin copolymer (COC), polyvinylidene fluoride (PVDF), polystyrene (PS), polycarbonate (PC), styrene dimethyl methacrylate copolymer (SMMA), cycloolefin polymer (COP), and styrene-ethylene / butylene-styrene block copolymer (SEBS).
[0228] This embodiment provides specific second polymer materials and third polymer materials.
[0229] In one embodiment, the first polymer material and the electroluminescent material are compounded to prepare an electroluminescent composite material;
[0230] The electroluminescent composite material is prepared into a preform, wherein the preform is provided with two or more holes (which may be double holes, three holes or four holes, etc.) along its axial direction, and preferably, the two or more holes are parallel to each other;
[0231] The conductive layer is passed through more than two holes of the preform rod respectively, and the electroluminescent fiber is prepared and obtained by a heat softening wire drawing method. Preferably, the conductive layer is a conductive wire.
[0232] This embodiment provides another method for preparing electroluminescent fibers. The preform is made of an electroluminescent composite material. Two or more conductive filaments pass through two or more holes respectively, and then are thermally softened and drawn to prepare the following method: Figure 2 , Figure 3 The light-emitting electroluminescent fiber has an equal structure, that is, two or more conductive fibers respectively form a conductive layer 1, and the electroluminescent composite material forms a light-emitting layer 2.
[0233] The method has the advantages of low production cost, simple operation, easy batch preparation, controllable wire diameter, controllable structure, and environmental friendliness.
[0234] In a specific embodiment, the preform is composed of two or more electroluminescent composite materials arranged along the axial direction thereof, and at least one of the electroluminescent composite materials has a different luminescent wavelength band from the other electroluminescent composite materials;
[0235] The hole is in contact with at least one of the electroluminescent composite materials.
[0236] This embodiment is a preferred solution of the previous embodiment. Electroluminescent materials with different luminescent wavelengths can emit light of different colors. After heat softening and drawing, different electroluminescent composite materials form luminescent layer units. Multiple luminescent layer units ( Figure 4-10 The light-emitting layer is distinguished by different color depths of different light-emitting layer units) to form the light-emitting layer 2. The conductive layers on both sides of different types of light-emitting units can be made conductive, so that the electroluminescent composite materials containing electroluminescent materials with different light-emitting bands can emit light of different colors, and different electroluminescent composite materials can also be made to emit light separately, or simultaneously, or alternately.
[0237] In a specific embodiment, the conductive wire is a metal wire having uneven defects distributed on its surface. In this embodiment, the uneven defects distributed on the surface of the metal wire can make the conductive layer 1 and the light-emitting layer 2 contact more closely, thereby increasing the adhesion between the two.
[0238] In a specific embodiment, the conductive wire is a metal wire, and a dielectric insulating layer with a high dielectric constant is coated on its surface;
[0239] Preferably, the material of the high dielectric constant dielectric insulating layer is a nano-coating selected from one or a combination of two or more of barium titanate (BaTiO3), lead titanate (PbTiO3), strontium titanate (SrTiO3), and titanium dioxide (TiO2).
[0240] In this embodiment, a dielectric insulating layer with a high dielectric constant is coated on the surface of the metal wire to prevent the light-emitting layer from being electrically broken down and causing fluorescence quenching.
[0241] In one embodiment, the preform outer shell is provided with a transparent material;
[0242] Preferably, the transparent material is a fourth polymer material.
[0243] Then, after heat softening and drawing, the transparent material forms a transparent protective layer located on the surface of the electroluminescent fiber, thereby protecting the luminescent layer 2 or the transparent conductive layer 3, increasing the durability of the electroluminescent fiber while ensuring that the light emitted from the luminescent layer can be transmitted.
[0244] In a specific embodiment, the fourth polymer material is a transparent thermoplastic polymer material, selected from one or more of polymethyl methacrylate (PMMA), fluororesin, fluororesin-modified polymethyl methacrylate (F-PMMA), cycloolefin copolymer (COC), polyvinylidene fluoride (PVDF), polystyrene (PS), polycarbonate (PC), styrene dimethyl methacrylate copolymer (SMMA), cycloolefin polymer (COP), and styrene-ethylene / butylene-styrene block copolymer (SEBS).
[0245] This embodiment provides a specific fourth polymer material.
[0246] In a specific embodiment, functional materials are added into the transparent material.
[0247] Functional materials refer to materials that have specific functions after being acted upon by light, electricity, magnetism, heat, chemistry, biochemistry, etc. Adding functional materials to transparent materials can make the transparent materials have the characteristics of functional materials, so that the formed outer transparent protective layer 4 can play more functions.
[0248] In a specific embodiment, the functional material is selected from one or a combination of two or more of a photoluminescent material, a fluorescent material, and a scattering agent;
[0249] Preferably, the scattering agent is selected from one or a combination of two or more of TiO2, BaSO4, Al2O3, MgO, BeO, Y2O3, ZrO2, GaAs, ZnS, ZnSe, MgF2, and CaF2.
[0250] When the functional material is a photoluminescent material, the outer protective layer on the surface of the prepared electroluminescent fiber contains the photoluminescent material, so that the luminescent spectrum (emitting light of different colors) and luminescent brightness of the electroluminescent fiber can be adjusted.
[0251] When the functional material is a fluorescent material, the outer protective layer on the surface of the prepared electroluminescent fiber contains the fluorescent material, so that the luminescent spectrum of the electroluminescent fiber can be adjusted.
[0252] When the functional material is a scattering agent, the outer protective layer on the surface of the prepared electroluminescent fiber contains the scattering agent, so that the light scattering angle of the electroluminescent fiber can be adjusted to make the light emission more uniform and soft.
[0253] In a specific embodiment, the electroluminescent material is a long afterglow material of a sulfide system, an alkaline earth metal sulfide, a sulfide material with a rare earth as an activator, a long afterglow material of an aluminate system, a long afterglow material of a silicate system, a long afterglow material of a gallate (gallium germanate) system, a long afterglow material of other systems such as a silicon-based oxynitride series, a stannate system, a phosphate system, a titanate system, a rare earth-doped or transition metal-doped upconversion luminescent material, and one or more of luminescent quantum dots.
[0254] This embodiment lists some types of electroluminescent materials that can be used in the method for preparing electroluminescent fibers of this application.
[0255] In a specific embodiment, the long afterglow material of the sulfide system includes a transition metal sulfide, and the transition metal sulfide is selected from ZnS:Cu 2+ 、ZnS:Mn 2+ or ZnS:Cu 2+ ,Co 2+ One or more of the following: and / or
[0256] Alkaline earth metal sulfide selected from CaS:Cu 2+ 、CaS:Ba 3+ or CaSrS:Ba 3+ One or more of the following: and / or
[0257] The rare earth sulfide material used as the activator is selected from Y2O2S:Eu 3+ Mg 2+ ,Ti 4+ 、CaS:Eu 2+ ,Pr 3+ 、CaS:Eu 2+ ,Tm 3+ One or more of the following: and / or
[0258] The long afterglow material of the aluminate system is selected from CaAl2O4:Eu 2+ ,Nd 3+ 、Sr3Al2O4:Eu 2+ ,Dy 3+ 、Sr4Al 14 O 25 :Eu 2+ ,Dy 3+ 、CaAl4O7:Ce 3+ 、MAlO3:Mn 4+ ,Ge 4+ (M=La, Gd) or more; and / or,
[0259] The long afterglow material of the silicate system is selected from MgSiO3:Mn2+ ,Eu 2+ ,Dy 3+ 、CdSiO3:Mn 2+ 、CdSiO3:Sm 2+ 、Ba2ZrSi3O9:Eu 2+ ,Pr 3+ One or more of the following: and / or
[0260] The long afterglow material of the gallate (gallium germanate) system is selected from ZnGa2O4:Cr 3+ 、Zn3Ga2Ge2O 10 :Cr 3+ 、Zn2Ga2Ge2O 10 :Cr 3+ ,Pr 3+ 、Mg4Ga8Ge2O 20 :Cr 3+ One or more of the following: and / or
[0261] Silicon-based oxynitride series include LaSi3N5:Ce 3+ and / or,
[0262] The stannate system is selected from Sr2SnO4:Sm 3+ 、CaSnO3:Pr 3+ One or more of the following: and / or
[0263] Titanate systems include CaTiO3:Pr 3+ and / or,
[0264] The up-conversion luminescent material is selected from one or more nanocrystals of NaYF4, NaGdF4, LiYF4, YF3, CaF2 fluoride or Gd2O3 oxide, such as NaYF4:Er, Yb, etc.; and / or,
[0265] The light-emitting quantum dots are selected from one or more of cadmium sulfide (CdS), cadmium selenide (CdSe), and cadmium telluride (CdTe).
[0266] This embodiment specifically lists some electroluminescent materials that can be used in the method for preparing electroluminescent fibers of this application.
[0267] In a specific embodiment, the electroluminescent composite material is prepared by physical blending, physical / chemical blending or solution blending.
[0268] The physical blending method is to uniformly mix the polymer material and the electroluminescent material under heating and melting conditions by a screw extruder, thereby preparing the electroluminescent composite material.
[0269] The physical / chemical blending method is that some chemical polymerization reactions will occur on the basis of physical blending, and the electroluminescent material does not participate in the chemical reaction, thereby enhancing the physical properties of the polymer to prepare the electroluminescent composite material.
[0270] The solution blending method is to use chemical reagents to fully dissolve the polymer material into a solution, then add the electroluminescent material and disperse it evenly by means of ultrasound or magnetic stirrer, etc. The polymer material and the electroluminescent material do not react with the chemical reagents. Then the chemical reagents are removed to prepare the electroluminescent composite material.
[0271] In a specific embodiment, the electroluminescent material accounts for 0.1 wt.% to 70 wt.% in the electroluminescent composite material, and can be 0.1 wt.%, 1 wt.%, 5 wt.%, 10 wt.%, 20 wt.%, 30 wt.%, 40 wt.%, 50 wt.%, 60 wt.%, 70 wt.%, preferably 20 wt.% to 50 wt.%.
[0272] In this embodiment, the mass ratio of the electroluminescent material in the electroluminescent composite material is 0.1wt.% to 70wt.%, within which the electroluminescent fiber can be prepared in batches and emit light uniformly. When the mass ratio is higher than this range, the electroluminescent fiber is difficult to prepare. In particular, when the mass ratio is preferably 20wt.% to 50wt.%, the mechanical properties are relatively superior while ensuring the luminescent performance. When the concentration is lower than 20wt%, the mechanical properties are good but the luminescent performance is poor, and when the concentration is higher than 50wt.%, the luminescent performance is good but the mechanical properties are relatively poor.
[0273] In a specific embodiment, the concentration distribution of the electroluminescent material in the electroluminescent composite material remains constant or gradually decreases or increases from the inside to the outside of the preform along the radial direction.
[0274] Through this technical solution, the luminescent layer in the prepared electroluminescent fiber can remain unchanged or gradually decrease or increase along the radial direction of the electroluminescent fiber from the inside to the outside. When the concentration distribution in the luminescent layer remains unchanged along the radial direction of the fiber from the inside to the outside, the electroluminescent fiber can be mass-produced and have excellent luminescent performance. When the concentration distribution in the luminescent layer gradually increases along the radial direction of the fiber, the luminescent performance of the electroluminescent fiber can be achieved while taking into account its mechanical properties. Compared with the concentration remaining unchanged along the radial direction of the fiber from the inside to the outside (comparing the outermost concentration), the luminescent performance is slightly weakened, but the mechanical properties are significantly improved. When the concentration distribution in the luminescent layer gradually decreases along the radial direction of the fiber, the luminescent performance of the electroluminescent fiber can be achieved while taking into account its mechanical properties. Compared with the concentration remaining unchanged along the radial direction of the fiber from the inside to the outside (comparing the outermost concentration), the mechanical properties are weakened but the luminescent performance is significantly improved.
[0275] In a specific embodiment, the first polymer material is selected from the polymer selected from polymethyl methacrylate (PMMA), fluororesin, PMMA composite material doped with fluorinated polymer (F-PMMA), styrene dimethyl methacrylate copolymer (SMMA), cycloolefin copolymer (COC), cycloolefin polymer (COP), polycarbonate (PC), polyphenylene sulfone resin (PPSU), polyether sulfone resin (PES), polyethylene imine (PEI), polystyrene (PS), polyethylene (PE), polypropylene (PP), polyamide (PA), polyimide (PI), polyethylene terephthalate (PET), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), styrene-ethylene / butylene-styrene block copolymer (SEBS), polyurethane (PU), polyvinyl chloride (PVC), polystyrene (PS), polypropylene terephthalate ( PTT), polyvinylidene chloride resin (PVDC), acrylonitrile-butadiene-styrene copolymer (ABS), polyethylene glycol (PEG), thermoplastic elastomer (TPE), low-density polyethylene (LDPE), polyethylene glycol (PEG), high-density polyethylene (HDPE), polyoxymethylene (POM), polyphenylene ether (PPO), polyester and sodium isophthalate sulfonate copolymer, acrylate copolymer, vinyl acetate resin, polyvinyl acetal, one or more of polymethyl methacrylate (PMMA), fluororesin, fluororesin-modified polymethyl methacrylate (F-PMMA), cycloolefin copolymer (COC), polyvinylidene fluoride (PVDF), polystyrene (PS), polycarbonate (PC), styrene dimethyl methacrylate copolymer (SMMA), cycloolefin polymer (COP), styrene-ethylene / butylene-styrene block copolymer (SEBS), etc.
[0276] In this embodiment, specific types of the first polymer material are given.
[0277] In a specific embodiment, the cross-section of the electroluminescent fiber is one of a circle, a triangle, a rectangle, an ellipse, and a five-pointed star.
[0278] In this embodiment, several cross-sectional shapes of the electroluminescent fiber are listed. In addition, the electroluminescent fiber of the present invention only needs to be filamentous, and its cross-sectional shape is not limited to the above-listed shapes.
[0279] The following are related embodiments of the electroluminescent yarn.
[0280] In one specific embodiment, an electroluminescent yarn is disclosed, wherein the electroluminescent yarn is made by twisting two or more electroluminescent fibers;
[0281] The electroluminescent yarn is selected from any one of the electroluminescent yarns mentioned above; and / or,
[0282] The electroluminescent yarn is selected from electroluminescent yarns prepared by any one of the above methods or two or more methods.
[0283] Yarn is a textile product that is made of various textile fibers and has a certain fineness. The electroluminescent yarn of this embodiment is made by twisting two or more electroluminescent fibers, so that it can be used for the subsequent preparation of fabrics.
[0284] The following are related implementations of the electroluminescent fabric.
[0285] In a specific embodiment, an electroluminescent fabric is disclosed, which contains electroluminescent fibers and / or electroluminescent yarns; or, the electroluminescent fabric contains transparent conductive fibers and electroluminescent fibers and / or electroluminescent yarns; wherein the electroluminescent fibers are selected from any one or two or more of the electroluminescent fibers described above; and / or, the electroluminescent fibers are selected from electroluminescent fibers prepared by any one or two or more of the methods described above; and the electroluminescent yarn is selected from the electroluminescent yarns described above.
[0286] Specifically, the electroluminescent fabric of this embodiment can be woven from the above electroluminescent fibers, or woven from the above electroluminescent yarns, or woven from the above electroluminescent fibers and electroluminescent yarns, or woven from transparent conductive fibers and electroluminescent fibers, or woven from transparent conductive fibers and electroluminescent yarns, or woven from transparent conductive fibers, electroluminescent fibers and electroluminescent yarns, and so on. The structure of the electroluminescent fabric prepared by the above combination can be as follows: Fig.11 shown.
[0287] It is known in the art that the electric field between the conductive layers in the electroluminescent fiber can be controlled to emit light.
[0288] The present invention provides an electroluminescent fiber having more than two conductive layers; and a luminescent layer disposed between the conductive layers, which has a simple structure, reliable performance, good luminescent effect, a firm combination of the luminescent layer and the conductive layer, and an optimized solution can realize different colors or color combinations separately or simultaneously. In addition, the present invention also provides a method for preparing the electroluminescent fiber, which has the advantages of low production cost, simple operation, easy batch preparation, controllable wire diameter, controllable structure, and environmental friendliness. In addition, the present invention uses the above-mentioned electroluminescent fiber to prepare electroluminescent yarn and electroluminescent fabric. The electroluminescent fabric of the present invention is not easily damaged in a bent and folded state, and has the characteristics of excellent wearability and luminescent effect.
[0289] Example
[0290] The experimental methods used below are conventional methods unless otherwise specified.
[0291] Unless otherwise specified, the materials and reagents used below can be obtained from commercial sources.
[0292] The fluororesin used in the following examples is PVDF (model 2850-00).
[0293] Example 1 (Electronic transparent conductive layer electroluminescent fiber, the electroluminescent material concentration in the luminescent layer is 50wt.%)
[0294] 1. Preparation of electroluminescent composite materials
[0295] (1) Weigh 35 g of polymethyl methacrylate (PMMA) and 15 g of fluororesin, and use a beaker to measure 200 mL of polydimethylacetamide (DMAC), add the polymethyl methacrylate and fluororesin into the beaker, mix with polydimethylacetamide (DMAC), place on a magnetic stirrer, heat and stir in a water bath at 80° C. until the particles are dissolved, and obtain a uniform mixed solution;
[0296] (2) Add 50 g of electroluminescent material (luminescent material model D502B, luminescent component ZnS:Cu, diameter 29 μm, luminescent band 502 nm), sourced from Shanghai Keyan Optoelectronic Technology Co., Ltd.) to the mixed solution, stir with a magnetic stirrer and then place in an ultrasonicator for ultrasonic dispersion for 15 min to obtain a mixed solution of polymethyl methacrylate (PMMA), fluororesin, polydimethylacetamide (DMAC) and electroluminescent material (ZnS:Cu);
[0297] (3) The mixed solution was scraped into a thin film with a scraper, dried for 72 hours, crushed into powder, dried in a ventilated oven at 50° C. for 24 hours, and dried in a vacuum oven at 50° C. for 24 hours to remove the solvent polydimethylacetamide (DMAC), to obtain an electroluminescent composite material with a concentration of 50 wt.%.
[0298] 2. Preparation of electronic transparent conductive materials
[0299] (1) Weigh 49 g of polymethyl methacrylate (PMMA) and 1 g of silver nanowires, and use a beaker to measure 200 mL of polydimethylacetamide (DMAC);
[0300] (2) polymethyl methacrylate (PMMA) and polydimethylacetamide (DMAC) were mixed, placed on a magnetic stirrer, and heated in an 80° C. water bath with stirring until the particles were dissolved to obtain a uniform mixed solution;
[0301] (3) adding 1 g of silver nanowire to the mixed solution of step (2) and fully dissolving;
[0302] (4) The mixed solution of step (3) is scraped into a thin film with a scraper, dried for 72 hours, crushed into powder, placed in a ventilated oven at 50° C. for 24 hours, and dried in a vacuum drying oven at 50° C. for 24 hours to remove the solvent polydimethylacetamide (DMAC), thereby obtaining an electronic transparent conductive material.
[0303] 3. Preparation of preform
[0304] 3.1 In this embodiment, a preform is prepared by hot pressing, which includes the following steps:
[0305] (1) The electroluminescent composite material is placed in a mold of 100 mm × 22 mm × 22 mm (length × width × height). The mold is a stainless steel groove, and the groove is covered with a Teflon film to prevent the polymer material from adhering to the mold after thermal softening.
[0306] (2) Cover the upper and lower sides of the mold containing the mixture with stainless steel plates and place it in a hot press to ensure uniform force during the pressurization process. Set the temperature on the hot press to 120°C, preheat the mixture in the mold at a pressure of 1 MPa for 3 minutes, then increase the pressure to 5 MPa, and repeat this step until the preform is formed, which is recorded as preform No. 1. Therefore, the width of preform No. 1 is 22 mm.
[0307] (3) The hot-pressed preform is taken out with a punch and placed in a drying oven for later use.
[0308] (4) According to the above steps (1-3), the electronic transparent conductive material is prepared into an outer transparent conductive layer preform rod, which is recorded as preform rod No. 2. The only difference is that the mold size is 100 mm×32 mm×32 mm (length×width×height), so the width of preform rod No. 2 is 32 mm.
[0309] (5) According to the above steps (1-3), the pure polymer material polymethyl methacrylate PMMA is prepared into an outer transparent protective layer preform rod, which is recorded as preform No. 3. The only difference is that the mold size is 100 mm×37 mm×37 mm (length×width×height), so the width of preform No. 3 is 37 mm.
[0310] 3.2 In addition, the preform can also be prepared by extrusion, which is only an example and includes the following steps:
[0311] Put the above electroluminescent composite material into a barrel, select a hollow structure mold with an outer diameter of 25mm, a hollow inner diameter of 22mm, and a length of 100mm, set the heating temperature to 180°C, put the barrel into an extruder, turn on the rod feeding, and melt extrude to obtain a preformed rod in the shape of the mold.
[0312] Those skilled in the art will know that by changing the outer diameter, inner diameter and other dimensions of the above-mentioned mold, the above-mentioned corresponding No. 1 preform rod, No. 2 preform rod or No. 3 preform rod can be produced.
[0313] 4. Preparation of preform with porous structure
[0314] (1) Place the preform rod No. 1 prepared in 3.1 in the lathe fixture, and process the preform rod by adjusting the rotation speed and feed distance. The lathe speed is 150-300r / min. The preform rod is processed into a circle with a cross-sectional area of 20mm and a length of 100mm.
[0315] (2) The preform rod processed by the lathe in (1) is axially drilled with a drill bit having a diameter of 1 mm. After processing by the drill bit, a hollow preform rod with an outer diameter of 20 mm and an inner diameter of 1.5 mm is obtained, which is recorded as preform rod No. 1'.
[0316] (3) According to the above steps (1-2), the preform No. 2 prepared in 3.1 is prepared into a hollow preform with an outer diameter of 30 mm and an inner diameter of 20 mm, which is recorded as preform No. 2'.
[0317] (4) According to the above steps (1-2), the No. 3 preform prepared in 3.1 is prepared into a hollow preform with an outer diameter of 35 mm and an inner diameter of 30 mm, which is recorded as No. 3' preform.
[0318] (5) The hollow structure preform rods of steps (2), (3) and (4) are combined by a sleeve method to obtain a final preform rod with a hole structure for heat softening and drawing, with an outer diameter of 35 mm and an inner diameter of 1.5 mm, that is, a preform rod with a hole structure, denoted as preform rod No. 4, and a radial hole is drilled 5 mm at the lower end of preform rod No. 4.
[0319] 5. Heat soften and draw the No. 4 preform in step 4, such as Fig.12 As shown, the following steps are included:
[0320] (1) A copper wire with a wire diameter of 50 μm is wound on a ring-shaped receiving coil, and the free end of the copper wire is passed through the through hole of a No. 4 preform rod with a hole structure fixed on the wire drawing equipment. The lower end of the No. 4 preform rod is radially inserted into the metal wire, and a 20 g weight is fixed at the lower end of the metal wire and the copper wire.
[0321] (2) Turn on the heating furnace, set the temperature of the upper temperature zone to 125°C, and the temperature of the lower temperature zone to 235°C. When the temperature of the heating zone reaches the preset temperature, lower the rod to a fixed length.
[0322] (3) After the preform rod with a hole structure is heated and softened, the material head falls down and passes through the diameter gauge 8 and the auxiliary traction 10 in sequence. The rod feeding speed is set to 0.1 mm / min and the stable wire collection speed is 0.25 m / min.
[0323] Thus, an electroluminescent fiber with an inner conductive layer diameter of 50 μm, a luminescent layer thickness of 175 μm, an outer transparent conductive layer thickness of 100 μm, an outer transparent protective layer thickness of 50 μm, and an overall wire diameter of 700 μm (the electroluminescent material concentration in the luminescent layer is 50 wt%) (structure as shown in FIG. Figure 1 shown).
[0324] Example 2 (Electronic transparent conductive layer electroluminescent fiber, the electroluminescent material concentration in the luminescent layer is 70wt.%)
[0325] In the electroluminescent fiber prepared in this embodiment, the concentration of the electroluminescent material in the middle light-emitting layer is 70wt.%, and the other steps are the same as in Example 1, that is, an electroluminescent fiber with an inner conductive layer diameter of 50μm, a light-emitting layer thickness of 175μm, an outer transparent conductive layer thickness of 100μm, an outer transparent protective layer thickness of 50μm, and an overall wire diameter of 700μm is prepared (the concentration of the electroluminescent material in the light-emitting layer is 70wt.%).
[0326] Example 3 (Electronic transparent conductive layer electroluminescent fiber, the electroluminescent material concentration in the inner layer of the luminescent layer is 70wt.%, and the electroluminescent material concentration in the outer layer is 50wt.%)
[0327] In the electroluminescent fiber prepared in this embodiment, the concentration distribution of the electroluminescent material in the middle luminescent layer decreases from the inside to the outside along the radial direction of the fiber. Specifically, the following steps are included:
[0328] 1. Prepare two electroluminescent composite materials according to step 1 in Example 1
[0329] The first electroluminescent composite material is an electroluminescent composite material with a concentration of 70 wt.% prepared by using 20 g of polymethyl methacrylate (PMMA), 10 g of fluororesin, and 70 g of electroluminescent material (luminescent material model D502B, luminescent component ZnS:Cu, diameter 29 μm, luminescent wavelength 502 nm).
[0330] The second electroluminescent composite material is prepared by using 35g of polymethyl methacrylate (PMMA), 15g of fluororesin, and 50g of electroluminescent material (luminescent material model D502B, luminescent component ZnS:Cu, diameter 29μm, luminescent band 502nm) to prepare an electroluminescent composite material with a concentration of 50wt.%
[0331] 2. Prepare an electronic transparent conductive material according to step 2 in Example 1.
[0332] 3. Preparing a preform, comprising the following steps:
[0333] (1) According to the steps 3.1(1)-(3) in Example 1, the first electroluminescent composite material (with a concentration of 70 wt.%) was prepared into an electroluminescent preform, which was denoted as preform No. 1. The only difference was that the mold size was 100 mm×12 mm×12 mm (length×width×height), so the width of preform No. 1 was 12 mm;
[0334] (2) According to the steps 3.1(1)-(3) in Example 1, a second electroluminescent composite material (with a concentration of 50 wt.%) was prepared into an electroluminescent preform rod, denoted as preform rod No. 2. The only difference was that the mold size was 100 mm×22 mm×22 mm (length×width×height), so the width of preform rod No. 2 was 22 mm.
[0335] (3) According to the steps of step 3.1 (4) in Example 1, the electronic transparent conductive material is prepared into an outer transparent conductive layer preform rod, which is recorded as preform rod No. 3. The only difference is that the mold size is 100 mm×32 mm×32 mm (length×width×height), so the width of preform rod No. 3 is 32 mm.
[0336] (4) According to the steps of step 3.1 (5) in Example 1, pure polymer material polymethyl methacrylate PMMA is prepared as an outer transparent protective layer preform, which is recorded as preform No. 4. The only difference is that the mold size is 100 mm×37 mm×37 mm (length×width×height), so the width of preform No. 4 is 37 mm.
[0337] 4. Preparation of a preform having a hole structure (sleeve method), comprising the following steps:
[0338] (1) As in step 4 of Example 1, preform rod No. 1 is processed on a lathe drill to obtain a hollow structure preform rod with an outer diameter of 10 mm and an inner diameter of 1.5 mm, which is recorded as preform rod No. 1';
[0339] (2) As in step 4 of Example 1, preform rod No. 2 is processed on a lathe drill to obtain a hollow structure preform rod with an outer diameter of 20 mm and an inner diameter of 10 mm, which is recorded as preform rod No. 2';
[0340] (3) As in step 4 of Example 1, the No. 3 preform is prepared into a hollow preform with an outer diameter of 30 mm and an inner diameter of 20 mm, which is recorded as No. 3' preform.
[0341] (4) As in step 4 of Example 1, the No. 4 preform is prepared into a hollow preform with an outer diameter of 35 mm and an inner diameter of 30 mm, which is recorded as No. 4' preform.
[0342] (5) The hollow structure preform rods of steps (1)(2)(3)(4) are combined by a sleeve method to obtain a final preform rod with a hole structure for heat softening drawing, with an outer diameter of 35 mm and an inner diameter of 1.5 mm, that is, a preform rod with a hole structure, denoted as preform rod No. 5, and a radial hole is punched 5 mm at the lower end of preform rod No. 5.
[0343] 5. Heat soften and draw the preform rod with hole structure.
[0344] The steps are the same as step 5 of Example 1, setting the rod feeding speed to 0.1 mm / min and the stable wire collection speed to 0.25 m / min.
[0345] The result is an electroluminescent fiber with an inner conductive layer diameter of 50 μm, a luminescent layer thickness of 175 μm, an outer transparent conductive layer thickness of 100 μm, an outer transparent protective layer thickness of 50 μm, and an overall wire diameter of 700 μm (the electroluminescent material concentration in the inner layer of the luminescent layer is 70wt.%, and the electroluminescent material concentration in the outer layer is 50wt.%).
[0346] Example 4 (Electronic transparent conductive layer electroluminescent fiber, the electroluminescent material concentration in the inner layer of the luminescent layer is 50wt.%, and the electroluminescent material concentration in the outer layer is 70wt.%)
[0347] In the electroluminescent fiber prepared in this embodiment, the concentration distribution of the electroluminescent material in the middle luminescent layer increases from the inside to the outside along the radial direction of the fiber. The specific steps are the same as those in Example 3, that is, an electroluminescent fiber with an inner conductive layer diameter of 50 μm, a luminescent layer thickness of 175 μm, an outer transparent conductive layer thickness of 100 μm, an outer transparent protective layer thickness of 50 μm, and an overall wire diameter of 700 μm is prepared (the electroluminescent material concentration in the inner layer of the luminescent layer is 50 wt.%, and the electroluminescent material concentration in the outer layer is 70 wt.%).
[0348] Example 5 (ionic transparent conductive layer electroluminescent fiber, the electroluminescent material concentration in the luminescent layer is 70wt%)
[0349] 1. Preparation of electroluminescent composite materials:
[0350] An electroluminescent composite material was prepared according to step 1 in Example 1, using 20 g of polymethyl methacrylate (PMMA), 10 g of fluororesin, and 70 g of electroluminescent material (luminescent material model D502B, luminescent component ZnS:Cu, diameter 29 μm, luminescent band 502 nm) to prepare an electroluminescent composite material with a concentration of 70 wt.%.
[0351] 2. Preparation of ionic transparent conductive materials
[0352] (1) Weigh 50 g of polycarbonate (PC), 200 g of acetonitrile, 18.75 g of lithium perchlorate (LiClO4), and 37.5 g of polymethyl methacrylate (PMMA);
[0353] (2) polycarbonate and acetonitrile were mixed, placed on a magnetic stirrer, and heated in a water bath at 80° C. and stirred until the particles were dissolved to obtain a uniform mixed solution;
[0354] (3) Add 18.75 g of lithium perchlorate (LiClO4) to the mixed solution of step (2) and fully dissolve;
[0355] (4) 37.5 g of polymethyl methacrylate (PMMA) was slowly added to the solution in step (3) and placed on a magnetic stirrer with the speed set to 1000 rpm for 24 h to fully dissolve.
[0356] (5) The mixed solution of step (4) is scraped into a thin film with a scraper, dried for 72 hours, crushed into powder, placed in a ventilated oven at 50° C. for 24 hours, and dried in a vacuum drying oven at 50° C. for 24 hours to remove the solvent acetonitrile, thereby obtaining an ionic transparent conductive material.
[0357] 3. Preparation of preform
[0358] (1) According to the steps 3.1(1)-(3) in Example 1, an electroluminescent composite material (with a concentration of 70 wt.%) was prepared into an electroluminescent preform, denoted as preform No. 1. The only difference was that the mold size was 100 mm×22 mm×22 mm (length×width×height), so the width of preform No. 1 was 22 mm.
[0359] (2) According to the steps of step 3.1 (4) in Example 1, the ionic transparent conductive material is prepared into an outer transparent conductive layer preform rod, which is recorded as preform rod No. 2. The only difference is that the mold size is 100 mm×32 mm×32 mm (length×width×height), so the width of preform rod No. 3 is 32 mm.
[0360] (3) According to the steps of step 3.1 (5) in Example 1, pure polymer material polymethyl methacrylate PMMA is prepared as an outer transparent protective layer preform, which is recorded as preform No. 3. The only difference is that the mold size is 100 mm × 37 mm × 37 mm (length × width × height), so the width of preform No. 3 is 37 mm.
[0361] 4. Preparation of preform with hole structure (sleeve method)
[0362] (1) As in step 4 of Example 1, preform rod No. 1 is processed on a lathe drill to obtain a hollow structure preform rod with an outer diameter of 20 mm and an inner diameter of 1.5 mm, which is recorded as preform rod No. 1';
[0363] (2) As in step 4 of Example 1, the No. 2 preform is prepared into a hollow preform with an outer diameter of 30 mm and an inner diameter of 20 mm, which is recorded as No. 2' preform.
[0364] (3) As in step 4 of Example 1, the No. 3 preform is prepared into a hollow preform with an outer diameter of 35 mm and an inner diameter of 30 mm, which is recorded as No. 3' preform.
[0365] (4) The hollow structure preform rods of steps (1), (2) and (3) are combined by a sleeve method to obtain a final preform rod with a hole structure for heat softening and drawing, with an outer diameter of 35 mm and an inner diameter of 1.5 mm, that is, a preform rod with a hole structure, denoted as preform rod No. 4, and a radial hole is punched 5 mm at the lower end of preform rod No. 4.
[0366] 5. Heat softening and drawing of preform rods with hole structures
[0367] (1) Wrap a copper wire with a wire diameter of 50 μm on a ring-shaped receiving coil, pass the free end of the copper wire through the through hole of a preform rod fixed on the wire drawing equipment, and radially insert the lower end of the preform rod into the metal wire. At the same time, fix a 20 g weight at the lower end of the metal wire and the copper wire.
[0368] (2) Turn on the heating furnace, set the temperature of the upper temperature zone to 125°C, and the temperature of the lower temperature zone to 235°C. When the temperature of the heating zone reaches the preset temperature, lower the rod to a fixed length.
[0369] (3) After the preform rod is heated and softened, the material head falls and passes through the diameter gauge 8 and the auxiliary traction 10 in sequence. The rod feeding speed is set to 0.1 mm / min and the stable wire collection speed is 0.25 m / min.
[0370] In the electroluminescent fiber prepared in this embodiment, the concentration of the electroluminescent material in the middle luminescent layer is 70wt.%, and the other steps are the same as in Example 1, that is, an electroluminescent fiber with an inner conductive layer diameter of 50μm, a luminescent layer thickness of 175μm, an outer transparent conductive layer thickness of 100μm, an outer transparent protective layer thickness of 50μm, and an overall wire diameter of 700μm is prepared (the concentration of the electroluminescent material in the luminescent layer is 70wt.%)
[0371] Example 6 (ionic transparent conductive layer electroluminescent fiber, the electroluminescent material concentration in the luminescent layer is 70wt%, the conductive fiber is treated and coated with a high dielectric constant dielectric insulating layer of barium titanate (BaTiO3))
[0372] In the electroluminescent fiber prepared in this embodiment, the concentration distribution of the electroluminescent material in the light-emitting layer is 70wt.%, and the specific steps are the same as those in Example 5, except that the conductive metal wire is coated with a layer of high dielectric constant dielectric insulating layer barium titanate (BaTiO3), that is, an electroluminescent fiber with an inner conductive layer diameter of 50μm, a light-emitting layer thickness of 175μm, an outer transparent conductive layer thickness of 100μm, an outer transparent protective layer thickness of 50μm, and an overall wire diameter of 700μm is prepared.
[0373] Example 7 (Dual Electrode Parallel Distribution)
[0374] 1. Prepare the electroluminescent composite material according to step 1 in Example 1
[0375] An electroluminescent composite material with a concentration of 50 wt.% was prepared using 35 g of polymethyl methacrylate (PMMA), 15 g of fluororesin, and 50 g of electroluminescent material (luminescent material model D502B, luminescent component ZnS:Cu, diameter 29 μm, luminescent band 502 nm).
[0376] 2. Preparation of preform
[0377] (1) According to the method of steps 3.1 (1) to (3) of Example 1, a preform of an electroluminescent composite material with a concentration of 50 wt.% was prepared, except that the mold size was 100 mm×26 mm×26 mm (length×width×height). Therefore, the width of the electroluminescent preform was 26 mm and the length was 100 mm, which was recorded as preform No. 1;
[0378] (2) According to the steps of step 3.1 (5) in Example 1, pure polymer material polymethyl methacrylate PMMA is prepared into an outer transparent protective layer preform rod, which is recorded as preform rod No. 2. The only difference is that the mold size is 100 mm×32 mm×32 mm (length×width×height). Therefore, the width of preform rod No. 2 is 27 mm.
[0379] 3. Preparation of hollow structure preform
[0380] (1) As in step 4 of Example 1, preform rod No. 1 is processed on a lathe drill to obtain a porous preform rod with an outer diameter of 24 mm and two holes inside the preform rod, each with a hole diameter of 1.5 mm (the two holes are symmetrically distributed on both sides of the center of the circle), which is recorded as preform rod No. 1';
[0381] (2) As in step 4 of Example 1, the No. 2 preform is prepared into a hollow preform with an outer diameter of 30 mm and an inner diameter of 24 mm, which is recorded as No. 2' preform.
[0382] (4) The hollow structure preform rods of steps (1) and (2) are combined by a sleeve method to obtain a final preform rod with a double-hole structure for heat softening drawing, with an outer diameter of 30 mm and a hole diameter of 1.5 mm. A radial hole is punched 5 mm at the lower end of the obtained hollow preform rod to obtain a preform rod with a double-hole structure, which is recorded as preform rod No. 3.
[0383] 4. Heat softening and drawing the hollow electroluminescent preform
[0384] (1) A copper wire with a wire diameter of 50 μm is wound around two annular receiving coils, the free end of the copper wire is passed through the through hole of a preform rod fixed on a wire drawing device, the lower end of the preform rod is radially inserted into the metal wire, and a 20 g weight (two coils) is fixed at the lower end of the metal wire and the copper wire;
[0385] (2) Turn on the heating furnace, set the temperature of the upper temperature zone to 125°C, and the temperature of the lower temperature zone to 235°C. When the temperature of the heating zone reaches the preset temperature, place the rod in a fixed length;
[0386] (3) After the preform rod is heated and softened, the material head falls and passes through the diameter gauge 8 and the auxiliary traction 10 in sequence. The rod feeding speed is set to 0.1 mm / min and the stable wire collection speed is 0.36 m / min.
[0387] Thus, an electroluminescent fiber with an outer transparent protective layer thickness of 50 μm, a luminescent layer thickness of 175 μm and a diameter of 500 μm is obtained, wherein there are two inner conductive layers (copper wires) with a diameter of 50 μm (structure as shown in FIG. Figure 2 shown).
[0388] Example 8 (two electrodes are arranged in parallel, and functional materials are added to the protective layer)
[0389] The specific steps of this embodiment are the same as those of Embodiment 7, with the only difference being that in the prepared electroluminescent fiber, the concentration distribution of the electroluminescent material in the light-emitting layer is 50wt.%, wherein a small amount of scattering agent TiO2 (with a concentration distribution of 2wt.%) is added to the outer transparent protective layer, that is, an electroluminescent fiber with an inner conductive layer diameter of 50μm (two copper wires), a light-emitting layer thickness of 175μm, an outer transparent protective layer thickness of 50μm, and an overall wire diameter of 700μm is prepared.
[0390] Example 9 (two electrodes are arranged in parallel, and the electrodes are carbon fibers)
[0391] The specific steps of this embodiment are the same as those of Embodiment 7, with the only difference being that the prepared electroluminescent fiber has two inner conductive carbon fibers with a diameter of 50 μm, a luminescent layer with a thickness of 175 μm, an outer transparent protective layer with a thickness of 50 μm, and an overall wire diameter of 700 μm.
[0392] Example 10 (two electrodes are arranged in parallel, and the electrodes are silver-plated yarns)
[0393] The specific steps of this embodiment are the same as those of Embodiment 7, with the only difference being that the prepared electroluminescent fiber has two inner conductive layer silver-plated yarns with a diameter of 50 μm, a luminescent layer with a thickness of 175 μm, an outer transparent protective layer with a thickness of 50 μm, and an overall wire diameter of 700 μm.
[0394] Example 11 (Three-electrode distribution)
[0395] 1. Prepare two electroluminescent composite materials according to step 1 in Example 1
[0396] The first method is to use 35g of polymethyl methacrylate (PMMA), 15g of fluororesin, and 50g of electroluminescent material (luminescent material model D417B, luminescent component ZnS:Cu, diameter 29μm, luminescent band 417nm) to prepare an electroluminescent composite material with a concentration of 50wt.%;
[0397] The second method is to use 35g of polymethyl methacrylate (PMMA), 15g of fluororesin, and 50g of electroluminescent material (luminescent material model D502B, luminescent component ZnS:Cu, diameter 29μm, luminescent band 502nm) to prepare an electroluminescent composite material with a concentration of 50wt.%.
[0398] 2. Preparation of preform
[0399] (1) According to the method of steps 3.1 (1) to (3) of Example 1, the two electroluminescent composite materials with a concentration of 50 wt.% were used to prepare preforms. The molds were both semi-cylindrical (with a diameter of 24 mm and a length of 100 mm), and were marked as preform No. 1 and preform No. 2, respectively.
[0400] (2) According to the method of step 3.1 (5) of Example 1, a preform rod is prepared using a transparent material (PMMA). The mold size is 100 mm×32 mm×32 mm (length×width×height). The width of the preform rod is 32 mm. It is marked as preform rod No. 3.
[0401] 3. Preparation of preform rods with hole structures
[0402] Same as step 4 of Example 1, preform No. 3 is processed on a lathe drilling table to obtain a preform with an outer diameter of 30 mm and an inner diameter of 24 mm. Preform No. 1 and preform No. 2 are combined with the processed preform No. 3 to prepare a solid core preform with an outer diameter of 30 mm (preform No. 3 is located in the cladding, and preform No. 1 and preform No. 2 are arranged side by side as the core layer). And after processing on a drilling table, a preform with a hole structure of three parallel holes is obtained (one hole is located between preform No. 1 and preform No. 2, and the other two holes are respectively divided into preform No. 1 and preform No. 2), and the hole diameters are all 1.5 mm.
[0403] 4. Heat softening and drawing of preformed rods with hole structures
[0404] As in step 5 of Example 1, the difference is that there are 3 wire feeding coils (copper wire), the rod feeding speed is set to 0.1 mm / min, and the stable wire collection speed is 0.36 m / min.
[0405] Thus, an electroluminescent fiber with a diameter of 500 μm is obtained, wherein the inner conductive layer has a diameter of 50 μm, the luminescent layer has a diameter of 400 μm (thickness of 175 μm), the outer transparent protective layer has a thickness of 50 μm, and the overall wire diameter is 500 μm. Figure 4 It can realize two-color luminescence, and realize the mixing and combination of two colors into multi-color luminescence.
[0406] Example 12 (Four-electrode square distribution)
[0407] 1. Preparation of electroluminescent composite materials
[0408] The electroluminescent composite material was prepared according to step 1 in Example 1 to prepare three electroluminescent composite materials.
[0409] The first one is an electroluminescent composite material with a concentration of 50 wt.% prepared by using 35 g of polymethyl methacrylate (PMMA), 15 g of fluororesin, and 50 g of electroluminescent material (luminescent material model D417B, luminescent component ZnS:Cu, diameter 29 μm, luminescent band 417 nm);
[0410] The second is an electroluminescent composite material with a concentration of 50wt.% using 35g of polymethyl methacrylate (PMMA), 15g of fluororesin, and 50g of electroluminescent material (luminescent material model D502B, luminescent component ZnS:Cu, diameter 29μm, luminescent band 502nm);
[0411] The third method is to use 35g of polymethyl methacrylate (PMMA), 15g of fluororesin, and 50g of electroluminescent material (luminescent material model D611B, luminescent component ZnS:Cu, diameter 29μm, luminescent band 611nm) to prepare an electroluminescent composite material with a concentration of 50wt.%.
[0412] 2. Preparation of preform
[0413] (1) According to the method of step 3.1 (5) of Example 1, a preform rod is prepared using PMMA. The mold size is 100 mm×32 mm×32 mm (length×width×height), and it is marked as No. 1;
[0414] (2) According to the method of steps 3.1(1)-(3) of Example 1, preform rods (respectively marked as preform rod No. 2, preform rod No. 3, and preform rod No. 4, where two preform rods No. 4 are prepared) are prepared using the above-mentioned electroluminescent composite material with a concentration of 50 wt.%, and the mold is in the shape of a quarter cylinder (with dimensions of 24 mm in diameter and 100 mm in length).
[0415] 3. Preparation of preform with hole structure
[0416] The same as step 4 of Example 1, the No. 1 preform rod is processed by a lathe drilling table to obtain a preform rod with an outer diameter of 30 mm and an inner diameter of 24 mm. The No. 2 preform rod, the No. 3 preform rod, and two No. 4 preform rods are combined with the processed No. 1 preform rod (the No. 1 preform rod is located in the cladding layer, the No. 2 preform rod, the No. 3 preform rod, and the two No. 4 preform rods are located in the core layer, and the two No. 4 preform rods are arranged opposite to each other), and a solid core preform rod with an outer diameter of 30 mm is prepared, and a preform rod with a hole structure of four holes distributed in a square shape is obtained after being processed by a drilling table (contacting the interfaces of the No. 2, No. 3, and No. 4 preform rods, respectively), and the hole diameters are all 1.5 mm.
[0417] 4. The preform rod with the hole structure is subjected to heat softening and wire drawing.
[0418] Same as step 5 of Example 1, except that there are four wire feeding coils, the feeding speed is set to 0.1 mm / min, and the stable wire collection speed is 0.36 m / min.
[0419] Thus, an electroluminescent fiber (such as Figure 8 As shown). It can realize three-color luminescence, and realize the mixing and combination of three colors into multi-color luminescence.
[0420] Example 13 (Four-electrode triangular distribution)
[0421] 1. Preparation of electroluminescent composite materials
[0422] The electroluminescent composite material was prepared according to step 1 in Example 1 to prepare three electroluminescent composite materials.
[0423] The first one is an electroluminescent composite material with a concentration of 50 wt.% prepared by using 35 g of polymethyl methacrylate (PMMA), 15 g of fluororesin, and 50 g of electroluminescent material (luminescent material model D417B, luminescent component ZnS:Cu, diameter 29 μm, luminescent band 417 nm);
[0424] The second is an electroluminescent composite material with a concentration of 50wt.% using 35g of polymethyl methacrylate (PMMA), 15g of fluororesin, and 50g of electroluminescent material (luminescent material model D502B, luminescent component ZnS:Cu, diameter 29μm, luminescent band 502nm);
[0425] The third method is to use 35g of polymethyl methacrylate (PMMA), 15g of fluororesin, and 50g of electroluminescent material (luminescent material model D611B, luminescent component ZnS:Cu, diameter 29μm, luminescent band 611nm) to prepare an electroluminescent composite material with a concentration of 50wt.%.
[0426] 2. Preparation of preform
[0427] (1) According to the method of step 3.1 (5) of Example 1, a preform rod was prepared using PMMA. The mold size was 100 mm × 32 mm × 32 mm (length × width × height), and it was marked as No. 1;
[0428] (2) According to the method of steps 3.1(1)-(3) of Example 1, preform rods (labeled as preform rod No. 2, preform rod No. 3, and preform rod No. 4, respectively) were prepared using the above-mentioned electroluminescent composite material with a concentration of 50 wt.%, and the mold was in the shape of one-third cylinder (with dimensions of 24 mm in diameter and 100 mm in length).
[0429] 3. Preparation of preform with hole structure
[0430] The same as step 4 of Example 1, the No. 1 preform rod is processed by a lathe drilling table to obtain a preform rod with an outer diameter of 30 mm and an inner diameter of 24 mm. The No. 2 preform rod, the No. 3 preform rod, and the No. 4 preform rod are processed by a lathe drilling table to form preform rods with fan-shaped symmetrical distribution and combined with the processed No. 1 preform rod (the No. 1 preform rod is located in the cladding layer, and the No. 2 preform rod, the No. 3 preform rod, and the No. 4 preform rod are located in the core layer) to prepare a solid core preform rod with an outer diameter of 30 mm, and the preform rod is processed by a drilling table to obtain a preform rod with a hole structure of four parallel holes (one hole is located at the intersection of the No. 2 preform rod, the No. 3 preform rod, and the No. 4 preform rod, and the other three holes are respectively divided into the No. 2 preform rod and the No. 3 preform rod and the No. 4 preform rod), and the hole diameter is 1.5 mm.
[0431] 4. The preform rod with the hole structure is subjected to heat softening and wire drawing.
[0432] Same as step 5 of Example 1, except that there are four wire feeding coils, the feeding speed is set to 0.1 mm / min, and the stable wire collection speed is 0.36 m / min.
[0433] Thus, an electroluminescent fiber (such as Fig.10 As shown). It can realize three-color luminescence, and realize the mixing and combination of three colors into multi-color luminescence.
[0434] Example 14 (Electroluminescent Yarn)
[0435] To prepare multi-color electroluminescent yarn, three electroluminescent fibers of different colors are twisted.
[0436] Three kinds of electroconductive fibers were prepared according to the steps of Example 1, except that:
[0437] The first type (denoted as A) is an electroluminescent composite material with a concentration of 50 wt.% prepared by using 35 g of polymethyl methacrylate (PMMA), 15 g of fluororesin, and 50 g of electroluminescent material (luminescent material model D417B, luminescent component ZnS:Cu, diameter 29 μm, luminescent band 417 nm).
[0438] The second type (denoted as B) is an electroluminescent composite material with a concentration of 50 wt.% prepared by using 35 g of polymethyl methacrylate (PMMA), 15 g of fluororesin, and 50 g of electroluminescent material (luminescent material model D502B, luminescent component ZnS:Cu, diameter 29 μm, luminescent band 502 nm);
[0439] The third type (denoted as C) uses 35g of polymethyl methacrylate (PMMA), 15g of fluororesin, and 50g of electroluminescent material (luminescent material model D611B, luminescent component ZnS:Cu, diameter 29μm, luminescent band 611nm), with a concentration of 50wt.% electroluminescent composite material.
[0440] Three electroluminescent fibers A, B, and C with a wire diameter of 500 μm were prepared. The diameter of the (inner) conductive layer (copper wire) was 50 μm, the diameter of the luminescent layer was 500 μm, the thickness of the luminescent layer was 225 μm, the thickness of the outer transparent conductive layer was 50 μm, and the overall wire diameter was 600 μm.
[0441] Electroluminescent fiber A, electroluminescent fiber B and electroluminescent fiber C are twisted to obtain multi-color electroluminescent yarn.
[0442] Experimental results analysis:
[0443] The prepared electroluminescent fiber embodiments 1-13 were subjected to optical performance tests and mechanical performance tests. Specifically, the optical performance was tested by connecting the inner and outer conductive layers of the electroluminescent fiber to the positive and negative electrodes of a high-voltage power supply, and a high-voltage AC power supply of 400V, 2kHz was passed through. During the test, the luminescence was measured, and the luminance of the luminescent fiber was recorded in real time using a brightness meter; the mechanical performance was tested by using an LC-202B universal material testing machine, and the prepared electroluminescent fiber was selected to be 10cm in length. The two ends of the fiber were fixed on the upper and lower chucks of the instrument, the lower chuck was fixed, and the upper chuck was adjusted to move up at a speed of 10mm / min. The load when the fiber broke was recorded during the stretching process. The specific experimental results are shown in Table 1.
[0444] Table 1: Performance analysis of electroluminescent fibers in different embodiments
[0445]
[0446] By comparing Examples 1 and 2, it can be seen that as the concentration of the electroluminescent material in the light-emitting layer increases, the luminous brightness of the light-emitting fiber is significantly improved, but its breaking strength is weakened.
[0447] Comparative Examples 1, 2, 3, and 4 show that the luminescent layer remains unchanged or gradually decreases or increases along the radial direction of the electroluminescent fiber from the inside to the outside. When the concentration distribution in the luminescent layer remains unchanged along the radial direction of the fiber from the inside to the outside, the excellent luminescent performance of the electroluminescent fiber can be achieved. When the concentration distribution in the luminescent layer gradually increases along the radial direction of the fiber, the luminescent performance of the electroluminescent fiber can be achieved while taking into account its mechanical properties. Compared with the concentration remaining unchanged along the radial direction of the fiber from the inside to the outside (comparing the outermost concentration), the luminescent performance is slightly weakened, but the mechanical properties are significantly improved. When the concentration distribution in the luminescent layer gradually decreases along the radial direction of the fiber, the luminescent performance of the electroluminescent fiber can be achieved while taking into account its mechanical properties. Compared with the concentration remaining unchanged along the radial direction of the fiber from the inside to the outside (comparing the outermost concentration), the mechanical properties are weakened but the luminescent performance is significantly improved.
[0448] By comparing Examples 2 and 5, it can be found that the luminous effect and mechanical properties are not greatly affected by whether the electronic conductive layer or the ionic conductive layer is used.
[0449] By comparing Examples 5 and 6, it can be found that the luminous brightness of the electroluminescent fiber with the conductive layer coated with barium titanate is significantly increased, and its mechanical properties are not greatly affected.
[0450] By comparing Examples 1 and 7, it can be found that the brightness of the dual-electrode luminescence is significantly higher than that of the coaxial structure electroluminescent fiber. However, during the test, it was found that the brightness of the dual-electrode electroluminescence along the circumference of the fiber is not as uniform as that of the coaxial structure.
[0451] By comparing Examples 7 and 8, it can be found that adding functional materials to the cladding can significantly improve the circumferential light uniformity of the electroluminescent fiber, but it also leads to limitations such as reduced brightness and weakened mechanical properties.
[0452] By comparing Examples 7, 9, and 10, it can be found that the luminous performance and mechanical properties are affected mainly by changing the conductive layer to different conductive materials. It can be found that the luminous effect and mechanical properties are not greatly affected.
[0453] Examples 11-14 are mainly for introducing multi-color effects, therefore, there is no need to test the luminous properties and mechanical properties.
[0454] The luminescence performance test, i.e., spectrum broadening test, was performed on Examples 11-14:
[0455] Specifically, the center of the three conductive layers of the electroluminescent fiber (Example 11) is a common end (saving one interface), and the three interfaces are connected to the positive and negative electrodes of two adjustable high-voltage power supplies to adjust the output voltage and frequency of the high-voltage amplifier power supply respectively. The energized electroluminescent fiber is connected to a visible-ultraviolet fiber spectrometer to test its spectrum.
[0456] For Example 12, the positive and negative electrodes of two adjustable high-voltage power supplies can be used.
[0457] For Examples 13 and 14, three adjustable high-voltage power supplies are used, wherein the central electrode of Example 13 is a common terminal (saving two interfaces). Six interfaces are connected to the positive and negative electrodes of the three adjustable high-voltage power supplies, respectively regulating the output voltage and frequency of the high-voltage amplifier power supply, and connecting the energized electroluminescent fiber to a visible-ultraviolet fiber spectrometer to test its spectrum.
[0458] Here, the results of Example 12 are listed as an example (eg Fig.13 ), the results of other cases 11, 13, and 14 can all achieve spectral broadening, and the results are similar, so they will not be repeated here.
[0459] Depend on Fig.13 It can be seen that as the voltage in the conductive layer in the tuning example 12 changes, it can be obviously found that the luminescence spectrum of the electroluminescent fiber appears to be broadened, and multi-color changes can be achieved.
[0460] In addition, after testing, the electroluminescent fibers prepared in the above Examples 1 to 14 can still maintain stable display brightness after working for 24 hours in an extreme environment of -30 to +90°C and a pH range of 0 to 14, and the luminous brightness can still be stable under 5000 Martindale wear cycles. The electroluminescent fibers of Examples 1 to 14 are not easily damaged in a bent or folded state (bending radius is less than 1 mm), and have excellent flame retardancy (burning rate is less than 39 mm / min, much less than 100 mm / min specified for automotive accessories), anti-electromagnetic interference, anti-ultraviolet aging, and excellent wearability.
[0461] Although the embodiments of the present application are described above, the present application is not limited to the above specific embodiments and application fields, and the above specific embodiments are merely illustrative and instructive, rather than restrictive. A person of ordinary skill in the art can make many forms under the guidance of this specification and without departing from the scope of protection of the claims of the present invention, all of which belong to the scope of protection claimed in the present application.
Claims
1. An electroluminescent fiber, comprising: Two or more conductive layers, wherein the conductive layers are conductive wires, and the conductive wires are metal wires, and the outer surfaces of the conductive wires have uneven defects; and A light-emitting layer, wherein the light-emitting layer contains a first polymer material and an electroluminescent material, and the light-emitting layer includes two or more light-emitting layer units arranged along the axial direction of the electroluminescent fiber, and the electroluminescent materials between at least one of the light-emitting layer units and the other light-emitting layer units have different light-emitting bands; wherein, Two or more conductive layers are arranged in the light-emitting layer along the axial direction of the electroluminescent fiber, and the conductive layer is in contact with at least one light-emitting layer unit so as to emit light of different wavelength bands; The outer surface of the conductive wire is coated with a dielectric insulation layer with a high dielectric constant, wherein the high dielectric constant refers to a dielectric constant greater than 10; The outermost layer of the electroluminescent fiber is coated with a transparent protective layer, and the transparent protective layer is a polymer material; Functional materials are added to the transparent protective layer, and the functional materials are evenly distributed in the transparent protective layer; the functional materials include scattering agents; The electroluminescent fiber is prepared by the following method: Compounding a first polymer material and an electroluminescent material to prepare an electroluminescent composite material; The electroluminescent composite material is prepared into a preform, wherein the outer cover of the preform is provided with a transparent material for forming the transparent protective layer, and the preform is provided with a hole structure along the axial direction thereof, wherein the hole structure includes more than two holes along the axial direction of the preform; The conductive layers are passed through more than two holes of the preform rod respectively, and the electroluminescent fiber is prepared and obtained by a heat softening wire drawing method.
2. The electroluminescent fiber according to claim 1, characterized in that: The first polymer material is selected from polymethyl methacrylate, fluororesin, PMMA composite material doped with fluorinated polymer, styrene dimethyl methacrylate copolymer, cycloolefin copolymer, cycloolefin polymer, polycarbonate, polyphenylene sulfone resin, polyether sulfone resin, polyethylene imine, polystyrene, polyethylene, polypropylene, polyamide, polyimide, polyethylene terephthalate, polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, styrene-ethylene / butylene-styrene block copolymer, polyurethane, polyvinyl chloride, polytrimethylene terephthalate, polyvinylidene chloride resin, acrylonitrile-butadiene-styrene copolymer, polyethylene glycol, thermoplastic elastomer, polyoxymethylene, polyphenylene ether, polyester and sodium isophthalate sulfonate copolymer, acrylate copolymer, vinyl acetate resin, polyvinyl acetal, or a combination of two or more thereof.
3. The electroluminescent fiber according to claim 1, characterized in that: The two or more conductive layers are arranged parallel to each other.
4. The electroluminescent fiber according to claim 1, characterized in that: The dielectric insulating layer material with a high dielectric constant is selected from one of barium titanate, lead titanate, strontium titanate, titanium dioxide, or a nano coating of a combination of two or more thereof.
5. The electroluminescent fiber according to claim 1, characterized in that: The transparent protective layer is a fourth polymer material, and the fourth polymer material is a transparent thermoplastic polymer material, selected from one or more of polymethyl methacrylate, fluororesin, polymethyl methacrylate modified by fluororesin, cycloolefin copolymers, polyvinylidene fluoride, polystyrene, polycarbonate, styrene dimethyl methacrylate copolymer, cycloolefin polymer, and styrene-ethylene / butylene-styrene block copolymer.
6. The electroluminescent fiber according to claim 5, characterized in that The functional material is uniformly distributed in the transparent protective layer.
7. The electroluminescent fiber according to claim 1, characterized in that: The functional material further comprises a photoluminescent material and / or a fluorescent material; and / or, The scattering agent is selected from one or a combination of two or more of TiO2, BaSO4, Al2O3, MgO, BeO, Y2O3, ZrO2, GaAs, ZnS, ZnSe, MgF2, and CaF2.
8. The electroluminescent fiber according to claim 1, characterized in that: The electroluminescent material accounts for 0.1wt.%-70wt.% by weight in the light-emitting layer; and / or, The concentration distribution of the electroluminescent material in the luminescent layer remains constant or gradually decreases or increases from the inside to the outside of the fiber radial direction.
9. The electroluminescent fiber according to claim 8, characterized in that The mass proportion of the electroluminescent material in the light-emitting layer is 20 wt.%-50 wt.%.
10. The electroluminescent fiber according to claim 1, characterized in that: The electroluminescent material is one or a combination of two or more of a sulfide system long afterglow material, alkaline earth metal sulfide, a sulfide material with rare earth as an activator, an aluminate system long afterglow material, a silicate system long afterglow material, a gallate system long afterglow material, a silicon-based oxynitride series, a stannate system, a phosphate system, a titanate system, a rare earth-doped or transition metal-doped up-conversion luminescent material, and a luminescent quantum dot.
11. The electroluminescent fiber according to claim 10, characterized in that The long afterglow material of the sulfide system includes a transition metal sulfide, wherein the transition metal sulfide is selected from ZnS:Cu 2+ 、ZnS:Mn 2+ 、ZnS:Cu 2+ ,Co 2+ One or a combination of two or more of the following: and / or Alkaline earth metal sulfide selected from CaS:Cu 2+ 、CaS:Ba 3+ 、CaSrS:Ba 3+ One or a combination of two or more of the following: and / or The rare earth sulfide material used as the activator is selected from Y2O2S:Eu 3+ , Mg 2+ , Ti 4+ 、CaS:Eu 2+ , Pr 3+ 、CaS:Eu 2+ ,Tm 3+ One or a combination of two or more of the following: and / or The long afterglow material of the aluminate system is selected from CaAl2O4:Eu 2+ , Nd 3+ 、Sr3Al2O4: Eu 2+ , Dy 3+ 、Sr4Al 14 O 25 :Eu 2+ , Dy 3+ 、CaAl4O7:Ce 3+ 、MAlO3:Mn 4+ , Ge 4+ (M=La, Gd) or a combination of two or more thereof; and / or, The long afterglow material of the silicate system is selected from MgSiO3:Mn 2+ , Eu 2+ , Dy 3+ 、CdSiO3:Mn 2+ 、CdSiO3:Sm 2+ 、Ba2ZrSi3O9:Eu 2+ , Pr 3+ One or a combination of two or more of the following: and / or The gallate system long afterglow material is selected from ZnGa2O4:Cr 3+ 、Zn3Ga2Ge2O 10 :Cr 3+ 、Zn2Ga2Ge2O 10 :Cr 3+ , Pr 3+ 、Mg4Ga8Ge2O 20 :Cr 3+ One or a combination of two or more of the following: and / or Silicon-based oxynitride series include LaSi3N5: Ce 3+ and / or, The stannate system is selected from Sr2SnO4:Sm 3+ or CaSnO3:Pr 3+ and / or, Titanate systems include CaTiO3:Pr 3+ and / or, The up-conversion luminescent material is selected from one or a combination of two or more nanocrystals of NaYF4, NaGdF4, LiYF4, YF3, CaF2 fluoride or Gd2O3 oxide; and / or, The light-emitting quantum dots are selected from one or a combination of two or more of cadmium sulfide, cadmium selenide and cadmium telluride.
12. The electroluminescent fiber according to any one of claims 1 to 11, characterized in that: The cross section of the electroluminescent fiber is one of a circle, a triangle, a rectangle, an ellipse and a five-pointed star.
13. The electroluminescent fiber according to claim 1, characterized in that The electroluminescent composite material is prepared by physical blending, physical / chemical blending or solution blending.
14. An electroluminescent yarn, wherein the electroluminescent yarn is made by twisting two or more electroluminescent fibers; The electroluminescent fiber is selected from any one or more of the electroluminescent fibers in claims 1 to 13.
15. An electroluminescent fabric, The electroluminescent fabric contains electroluminescent fibers and / or electroluminescent yarns; or, the electroluminescent fabric contains transparent conductive fibers and electroluminescent fibers and / or electroluminescent yarns; in, The electroluminescent fiber is selected from any one or more electroluminescent fibers in claims 1 to 13; the electroluminescent yarn is the electroluminescent yarn described in claim 14.
Citation Information
Patent Citations
A method for preparing luminescent fibers and fabrics
CN104674539B
Titanium / silicon dioxide-based flexible electroluminescence nanofiber
CN106883852A
Flexible electroluminescent device and preparation method thereof
CN107275498A
High-elasticity electroluminescent fiber and preparation method thereof
CN108093535A
Luminous color changing fabric and preparation method thereof
CN108505187A